Manufacturing method of laminated glass for automobile windows, laminated glass for automobile windows, and automobile
The method of pre-treating glass plates with controlled micro-cracking and lamination addresses uneven strength distribution in automotive window glass, enhancing impact absorption and safety for pedestrians and cyclists.
Patent Information
- Application Number
- JP2023515453
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-20
- Filing Date
- 2022-04-15
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2042-04-15
AI Technical Summary
Automotive window glass often has uneven strength distribution, leading to high-strength areas that fail to absorb impact during collisions, potentially causing harm to pedestrians and cyclists.
A manufacturing method involving the pre-treatment of glass plates with controlled micro-cracking to uniformize strength distribution, followed by bending and lamination, ensuring uniform stress absorption during impacts.
The method enhances the glass's ability to absorb impact uniformly, reducing the risk of high-strength areas and maintaining overall robustness, thus improving safety for pedestrians and cyclists.
Smart Images

Figure 0007626205000005 
Figure 0007626205000006 
Figure 0007626205000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing laminated glass for automobile windows, laminated glass for automobile windows, and an automobile. [Background technology]
[0002] Automobiles are required to have safety performance not only from the viewpoint of protecting passengers but also from the viewpoint of protecting the body of a pedestrian in the event of a collision with the pedestrian. In response to such a requirement, for example, Patent Document 1 proposes a configuration in which, when a pedestrian collides head-on with an automobile and a downward impact is applied from the front to the periphery of the cowl louvers and the windshield glass, the connected cowl louvers and the windshield are separated, thereby ensuring the body protection performance of the pedestrian. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-213928 A Summary of the Invention [Problem to be solved by the invention]
[0004] According to recent accident investigations, it has been reported that when a cyclist or motorcycle rider crashes head-on into a car, the cyclist's body is more likely to collide with the car at a higher position than a pedestrian, i.e., the cyclist's body is more likely to collide with the windshield (front glass). Furthermore, due to the structure of recent cars with short front noses, pedestrians are also more likely to collide with the windshield. Therefore, window glass such as windshields is also required to improve the body protection performance for pedestrians and cyclists (hereinafter also referred to as pedestrians, etc.). Here, in order to improve the body protection performance of laminated glass for automobile windows such as windshields, it is important that the glass sheets themselves absorb the impact by appropriately breaking during a collision, and that the interlayer film between the glass sheets also exhibits the functions of impact absorption and penetration prevention, thereby reducing the impact and damage to the bodies of pedestrians, etc.
[0005] However, it is known that glass sheets inherently have a strength distribution within their plane, and the strength of glass sheets is usually determined probabilistically based on the safety factor, breakage probability, etc. Therefore, even if the strength of the window glass as a whole is appropriate, there may be localized areas within the plane of the window glass where the strength is excessively high (hereinafter also referred to as high-strength areas), and when a pedestrian or the like collides into such a high-strength area, the window glass is not likely to break, so the window glass is unable to absorb the impact and the interlayer film is unable to perform its function, which may increase the possibility of injury to the human body.
[0006] In order to reduce the strength in the high strength region as described above, it is possible to reduce the strength of the automobile window glass as a whole by changing the composition or manufacturing method of the glass. However, in that case, the strength is also reduced in the region where the strength in the plane is relatively low, so there is a possibility that the robustness required for the automobile window glass cannot be secured. Therefore, there is a demand for automobile window glass with high safety performance in the event of a collision from the viewpoint of protecting the body of pedestrians, etc. as described above, by reducing or eliminating the region where the strength is excessively high and making the strength distribution in the plane as uniform as possible.
[0007] An object of one aspect of the present invention is to obtain a laminated glass for automobile windows that has the robustness required for automobile window glass and also has high bodily protection performance for pedestrians and the like in the event of a collision. [Means for solving the problem]
[0008] One aspect of the present invention is a method for producing laminated glass for automobile windows, comprising step (A) of heating and bending two glass sheets, and step (B) of laminating the two bent glass sheets together via an interlayer film, wherein prior to step (A), at least one of the two flat glass sheets is transported by a transport means while a surface of the at least one glass sheet facing the transport means is scratched by the transport means, and in step (B), the surface of the glass sheet facing the transport means is positioned so that it faces the interior side of the automobile when the laminated glass for automobile windows is installed in the automobile. Effect of the Invention
[0009] According to one aspect of the present invention, it is possible to provide a laminated glass for automobile windows which has the robustness required for automobile window glass and has high bodily protection performance for pedestrians and the like in the event of a collision. [Brief description of the drawings]
[0010] [Figure 1] 1 is a front view of an automobile equipped with a laminated glass according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of the laminated glass shown in FIG. [Diagram 3] FIG. 1 is a flow diagram of an example of a method for producing laminated glass according to embodiment a of the present invention. [Figure 4] FIG. 2 is a schematic diagram of an example of a conveying means used in embodiment a. [Diagram 5] FIG. 4 is a diagram illustrating an example of a conveying roller. [Figure 6] FIG. 4 is a diagram illustrating an example of a conveying roller. [Figure 7] 11A and 11B are diagrams illustrating an example of a damage inflicting function of a transport means. [Figure 8] 13A and 13B are diagrams illustrating another example of the damage applying function of the conveying means. [Figure 9] FIG. 2 is a flow diagram of an example of a method for producing laminated glass according to embodiment b of the present invention. [Figure 10] FIG. 13 is a schematic diagram showing an example of a scratching process used in embodiment b. [Figure 11] FIG. 13 is a diagram showing the frequency distribution of the intensities of Examples a1-1 and a1-2. [Figure 12] FIG. 13 is a diagram showing the frequency distribution of the intensities of Examples a2-1 and a2-2. [Figure 13] 13 is a graph showing the results of experiment a. [Figure 14] FIG. 13 is a diagram showing the frequency distribution of the intensities of Examples b1-1 and b1-2. [Figure 15] FIG. 13 is a diagram showing the frequency distribution of the intensities of examples b2-1 and b2-2. [Figure 16] 13 is a graph showing the results of experiment b. [Figure 17] 13 is a graph showing the results of experiment c. [Figure 18] 13 is a graph showing the results of experiment c. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] <Basic structure of laminated glass> First, the basic structure of the laminated glass for automobile windows will be described. Fig. 1 shows an example in which the laminated glass for automobile windows 1 manufactured according to one embodiment of the present invention is used as the window glass of an automobile 100. In the example of Fig. 1, the laminated glass for automobile windows 1 is glass installed in an opening (window) at the front of the body of the automobile 100, that is, a windshield, but the laminated glass for automobile windows 1 according to this embodiment can also be used as window glass other than the windshield, for example, a side glass, a rear glass, or a roof glass.
[0012] Fig. 2 shows a partial cross-sectional view of the laminated glass for automobile windows 1 shown in Fig. 1. As shown in Fig. 2, the laminated glass for automobile windows 1 may be formed by bonding an exterior glass sheet 10 and an interior glass sheet 20 together via an interlayer film 30. As shown in Fig. 2, the exterior glass sheet 10 has a first surface 11 that is the surface facing the exterior of the vehicle and a second surface 12 that is the surface facing the interior of the vehicle, and the interior glass sheet 20 has a third surface 21 that is the surface facing the exterior of the vehicle and a fourth surface 22 that is the surface facing the interior of the vehicle.
[0013] The material constituting the exterior glass plate 10 and the interior glass plate 20 (hereinafter, collectively referred to as glass plates) in the laminated glass 1 is preferably inorganic glass. Examples of inorganic glass include soda lime silicate glass, aluminosilicate glass, borate glass, lithium aluminosilicate glass, and borosilicate glass. The method for forming the glass plate made of inorganic glass is not particularly limited, but the glass plate is preferably formed by, for example, a float method. The glass plate may be unreinforced glass (raw glass). Unreinforced glass is glass obtained by forming molten glass into a plate shape and slowly cooling it, and is not subjected to a strengthening treatment such as air-cooling strengthening treatment or chemical strengthening treatment. By using unreinforced glass, even if the glass is broken by impact, the entire surface does not shatter into small pieces, and the visibility of the occupants can be secured even in the event of an accident.
[0014] The thicknesses of the exterior glass sheet 10 and the interior glass sheet 20 may be the same or different from each other. The thickness of the exterior glass sheet 10 may be 1.1 mm or more and 3.5 mm or less. The thickness of the interior glass sheet 20 may be 0.5 mm or more and 2.3 mm or less. Furthermore, the overall thickness of the laminated glass for automobile windows 1 may be 2.3 mm or more and 8.0 mm or less. The configurations of the exterior glass sheet 10 and the interior glass sheet 20 (materials constituting the glass sheets, manufacturing method of the glass sheets, etc.) may be the same or different from each other.
[0015] The material of the intermediate film 30, which is disposed between the vehicle exterior glass plate 10 and the vehicle interior glass plate 20 and bonds the vehicle exterior glass plate 10 and the vehicle interior glass plate 20, is not particularly limited, but is preferably a thermoplastic resin. Examples of the material of the intermediate film 30 include thermoplastic resins that have been used for various applications, such as plasticized polyvinyl acetal resins, plasticized polyvinyl chloride resins, saturated polyester resins, plasticized saturated polyester resins, polyurethane resins, plasticized polyurethane resins, ethylene-vinyl acetate copolymer resins, ethylene-ethyl acrylate copolymer resins, cycloolefin polymer resins, and ionomer resins. In addition, a resin composition containing a modified block copolymer hydrogenated product described in Japanese Patent No. 6065221 can also be preferably used. Among these, plasticized polyvinyl acetal resins are preferably used because they have an excellent balance of various performances such as transparency, weather resistance, strength, adhesive strength, penetration resistance, impact energy absorption, moisture resistance, heat insulation, and sound insulation. The above thermoplastic resins may be used alone or in combination of two or more. The term "plasticized" in the plasticized polyvinyl acetal resin means that the resin is plasticized by adding a plasticizer. The same applies to other plasticized resins.
[0016] The intermediate film 30 may be a resin that does not contain a plasticizer, such as an ethylene-vinyl acetate copolymer resin. Examples of the polyvinyl acetal resin include polyvinyl formal resin obtained by reacting polyvinyl alcohol (PVA) with formaldehyde, polyvinyl acetal resin in the narrow sense obtained by reacting PVA with acetaldehyde, and polyvinyl butyral resin (PVB) obtained by reacting PVA with n-butylaldehyde. In particular, PVB is a suitable material because it has an excellent balance of various properties such as transparency, weather resistance, strength, adhesive strength, penetration resistance, impact energy absorption, moisture resistance, heat insulation, and sound insulation. The above resins may be used alone or in combination of two or more kinds.
[0017] A shielding layer may be provided on the periphery of the laminated glass for automobile windows 1 to protect a sealant or the like that adheres and holds the laminated glass for automobile windows 1 to the vehicle body. The shielding layer may be formed, for example, by applying a ceramic color paste of a low brightness color such as black, gray, or brown, which contains a fusible glass frit containing a black pigment, and then firing the paste. The shielding layer may be formed on the periphery of one or more of the second surface 12, the third surface 21, and the fourth surface 22 (FIG. 2) of the laminated glass for automobile windows 1, preferably on the periphery of at least one of the second surface 12 and the fourth surface 22. The shielding layer may be provided over a range of 10 mm to 300 mm from the peripheral edge of the glass sheet.
[0018] 2, the laminated glass for automobile windows 1 may be curved as a whole or in part so as to be convex toward the exterior side of the vehicle. In this case, the exterior side glass sheet 10 and the interior side glass sheet 20 can be curved to a desired predetermined curvature in one direction or two directions by a bending forming process described later.
[0019] <Method of manufacturing laminated glass for automobile windows> Embodiment A A method for producing laminated glass for automobile windows according to embodiment a, which is one embodiment of the present invention, will be described. Fig. 3 shows a flow diagram of one example of the method for producing laminated glass for automobile windows according to embodiment a. As shown in Fig. 3, the production method according to embodiment a includes a step (A) of bending a flat glass sheet, and a step (B) of bonding two bent glass sheets together. This production method also includes a step (p) of preparing a flat glass sheet to be subjected to the bending step (A) as a pre-step of the bending step (A).
[0020] As shown in FIG. 3, the flat glass sheet preparation step (p) may include manufacturing a long belt-shaped glass sheet by a float method, a roll-out method, or the like (p1), annealing the belt-shaped glass sheet (p2), cutting out a blank sheet from the belt-shaped glass sheet (p3), cutting the blank sheet into a desired shape (p4), chamfering (p5), cleaning (p6), and printing a shielding layer (p7). These steps p1 to p7 are only an example, and the order of each step p1 to p7 may be partially changed. In addition, some of these steps may be changed or omitted, and additional steps other than steps p1 to p7 may be included at any timing of steps p1 to p7. For example, one or more additional cleaning steps other than the cleaning step (p6) may be added at any timing after the end of the annealing step (p2) and before the chamfering (p5).
[0021] Conventionally, various safety-related properties and functions have been required for laminated glass for automobile windows, but the requirements are becoming greater. In particular, in recent years, importance has been attached not only to the viewpoint of passenger protection but also to the viewpoint of protecting the body of pedestrians (pedestrians, cyclists, etc.) when they collide. Laminated glass for automobile windows is also required to satisfy specific standards such as the Head Injury Criterion (HIC), on the premise that it has appropriate robustness as automobile window glass. For example, a HIC value of less than 1,000, preferably less than 650, may be required in a specific region of laminated glass for automobile windows. Here, in order to improve the body protection performance of pedestrians, etc. in the event of a collision, it is important that the region (high strength region) with excessively high strength in the laminated glass for automobile windows is reduced or eliminated, and the distribution of strength in the plane direction is suppressed (the strength distribution is narrowed), that is, the strength in the plane is made as uniform or level as possible.
[0022] In contrast, the manufacturing method of laminated glass for automobile windows according to this embodiment includes scratching the surface of a flat glass sheet before the bending process (A). In this specification, "scratching" refers to a process of forming fine cracks (also called microcracks, which are fine cracks on the order of micrometers or less that cannot be visually recognized) on the surface of the glass sheet. In this embodiment, scratching the surface of the glass sheet can make the strength of the glass sheet and the laminated glass obtained using the glass sheet uniform or level across the surface. Originally, fine cracks exist on the surface of the glass sheet after production, and it is said that the uneven distribution of these fine cracks is the cause of the variation in strength of glass for automobile windows. However, according to the manufacturing method according to this embodiment, it is considered that the strength of the region where the strength is excessively high (high strength region) can be reduced by introducing new fine cracks into the surface of the glass sheet by scratching. On the other hand, scratching in this embodiment is a process that does not further reduce the strength of the region where the strength is relatively low (low strength region), or hardly reduces it at all. Therefore, by carrying out the scratching treatment in this embodiment, the strength of the glass sheet or the obtained laminated glass can be made uniform within the plane, and the strength required for automobile window glass can be maintained. As a result, it is possible to provide an automobile window laminated glass that has the robustness required for automobile window glass and also has the performance to ensure the physical safety of pedestrians and the like in the event of a collision with the pedestrians and the like.
[0023] In this embodiment, the scratching treatment is performed on at least one of the two flat glass sheets that form the laminated glass, the surface that faces the inside of the vehicle when the laminated glass is attached to the vehicle. For example, when a pedestrian or the like collides with the windshield of the vehicle from the outside of the vehicle, the impact of the collision is transmitted in sequence from the first surface 11 of the exterior glass sheet 10, which is the outermost surface, to the fourth surface 22 (FIG. 2) of the interior glass sheet 20, which is the innermost surface. At this time, in the exterior glass sheet 10, a compressive stress against a compressive force that contracts the area occurs on the first surface 11, and conversely, a tensile stress against a tensile force that expands the area occurs on the second surface 12, so that the exterior glass sheet 10 is likely to start cracking from the second surface 12 on the inside of the vehicle. For this reason, it is preferable that the second surface 12 is appropriately susceptible to cracking upon collision, that is, there is no or little high-strength region in which the strength is excessively high locally on the second surface 12. Similarly, when focusing on the interior glass sheet 20, a compressive stress against a compressive force that contracts the area occurs in the third surface 21, and a tensile stress against a tensile force that expands the area occurs in the fourth surface 22, so that the interior glass sheet 20 is likely to start cracking from the fourth surface 22 on the interior side of the vehicle. Therefore, it is preferable that the fourth surface 22 is appropriately susceptible to cracking during a collision, that is, there is no or little high-strength area in which the strength is excessively high locally in the fourth surface 22. Therefore, in this embodiment, from the viewpoint of protecting the bodies of pedestrians and the like during a collision, at least one of the second surface 12 on the interior side of the exterior glass sheet 10 and the fourth surface 22 on the interior side of the interior glass sheet 20 is scratched. Furthermore, if it is only one of the second surface 12 and the fourth surface 22, it is more preferable to scratch the second surface 12, which is more affected by the impact during a collision, and it is even more preferable to scratch both the second surface 12 and the fourth surface 22.
[0024] The glass plate to which the scratching process is applied in this embodiment is in a flat state before being bent. That is, the scratching process is applied to the flat surface of the glass plate, not to the curved surface of the glass plate. The scratching process is preferably applied to the entire surface of the glass plate in order to make the strength in the surface more uniform. However, if the scratching process is applied to the curved surface of the glass body evenly, it becomes necessary to change the direction in which the scratching means faces or the scratching means itself according to the curve of the curved surface, which tends to make the process complicated. Furthermore, in this embodiment, the scratching process is applied to at least one of the second surface 12 and the fourth surface 22 as described above, which will be the surface on the inside of the vehicle when the laminated glass is obtained in the subsequent lamination process (B), but the surface on the inside of the vehicle is a concave surface (FIG. 2). And, when trying to process the concave surface, it is even more difficult to perform scratching according to the curve of the curved surface, which tends to limit the configuration of the scratching means. Therefore, scratching the concave surface may result in an area that is not scratched, leaving a high-strength area, or conversely, the concave surface may be scratched so that the strength is excessively reduced and the required robustness cannot be obtained. In contrast, scratching the flat surface of a glass plate is relatively easy since there is no need to take into account the curvature of the surface, and the effort and cost required to configure scratching means can be reduced.
[0025] In the embodiment a, the above-mentioned scratching treatment can be carried out by the conveying means in the flat glass sheet preparation step (p).
[0026] The conveying means is a means for moving the belt-shaped glass sheet or glass sheet in a predetermined direction and conveying it from one processing device to the next processing device in the flat glass sheet preparation step (p). The conveying means may be a continuous means throughout the preparation step (p) or may be discontinuous. The conveying means in this embodiment is preferably a conveying means for supporting and conveying the belt-shaped glass sheet or glass sheet from below. Specific examples of the conveying means include a roller conveyor and a belt conveyor. Among these, it is preferable that a roller conveyor is used in at least a part of the production line of the flat glass sheet preparation step (p) because the conveying speed can be easily controlled. The roller conveyor can convey the glass sheet at a speed of 0.01 m / s or more and 2 m / s or less.
[0027] FIG. 4 shows a roller conveyor 50 as an example of the conveying means. As shown in FIG. 4, the roller conveyor 50 includes a plurality of conveying rollers 51, 51, ... each extending in a direction perpendicular to the conveying direction Dt and arranged in parallel in the conveying direction Dt. The flat glass sheet G, G, ... is placed on the conveying rollers 51, 51, ... and supported by the conveying rollers 51, 51, .... At least a part of the conveying rollers 51, 51, ... is rotated, and the flat glass sheet G, G, ... is conveyed in the conveying direction Dt by the frictional force generated by the contact between the peripheral surface of the conveying rollers 51, 51, ... and the conveying means facing surface of the glass sheet G, G, ... facing the roller conveyor (conveying means) 50. In this embodiment, at least a part of the conveying rollers 51, 51, ... has a scratching function for the scratching process described above in addition to a conventional conveying function. In the example of Figure 4, a conveying means is shown for conveying the glass plates G, G, ... after they have been cut into a shape for a windshield from the raw plate cut out in the cutting process (p3) (after the outline cutting process p4).
[0028] In the roller conveyor as a conveying means for glass sheets, the radius of the conveying roller may be about 10 mm or more and 20 cm or less, depending on the size, thickness, etc. of the glass sheet to be conveyed. It is preferable that at least the surface material of the conveying roller is made of a rubber-like body (a material such as rubber that has a large friction resistance against glass and has elasticity). For example, a sheet-like rubber-like body that is continuous in the axial direction Da of the conveying roller (a direction perpendicular to the conveying direction Dt in the roller conveyor of FIG. 4) may be wound around a shaft body made of metal, resin, etc., a band-like or string-like rubber-like body may be wound discontinuously in the axial direction Da in a spiral shape, or a ring-like rubber-like body may be attached to the roller shaft part with or without spacing in the axial direction Da. In this way, the rubber-like body is arranged on the circumferential surface of the shaft body and is configured to contact the glass sheet, thereby playing a role of preventing slippage and preventing scratches that would impair the strength of the glass sheet as window glass. In addition, the entire conveying roller may be made of a rubber-like body.
[0029] Figures 5 and 6 show an example of a conveying roller 51 in which a rubber-like material is disposed on the circumferential surface of a shaft. As shown in Figures 5 and 6, in the case of a conveying roller including a rubber-like material, the diameter D and radius r of the conveying roller 51 respectively refer to the diameter and radius in the configuration including the rubber-like material.
[0030] In the example shown in Fig. 5, a string-like rubber body 511 having a substantially circular cross section is wound in a spiral shape around a shaft body 515. In this case, it is preferable that the rubber body 511 is wound at intervals d of 500 mm or less when viewed in the axial direction Da (direction perpendicular to the conveying direction Dt). The length (width) w of the rubber body 511 in the axial direction Da may be 2 mm or more and 50 mm or less. The width w may be the length (width) in the axial direction Da where the rubber body continuously contacts the glass plate during conveyance of the flat glass plate.
[0031] In the example shown in Fig. 6, a plurality of ring-shaped or cylindrical rubber bodies 511, 511, ... are attached around the shaft body 515 at a predetermined interval. In this case, the distance d between the plurality of rubber bodies 511 in the axial direction Da may be 500 mm or less. In the case of the conveying roller 51 shown in Fig. 6, it is preferable that there are a plurality of conveying rollers equipped with such a scratching function. Furthermore, it is preferable that the positions of the rubber bodies 511, 511, ... are shifted in the axial direction Da between the plurality of conveying rollers, because this allows the flat glass plate to be scratched more evenly across the axial direction Da.
[0032] In addition, adjacent transport rollers may be in contact with each other or may be spaced apart, and when the transport rollers are spaced apart, the distance between the transport rollers may be 50 cm or less. The angular velocity of the transport rollers used as a normal transport means is 0.2 rad / s or more and 40 rad / s or less, depending on the diameter of the transport roller and the condition of the glass sheet being transported.
[0033] In the present manufacturing method, the scratching is performed in the step (p) of preparing a flat glass sheet, but more specifically, it can be performed at any timing after the above-mentioned annealing step (p2) and before the bending step (A). That is, if the scratching is performed on the surface of the flat glass sheet facing the conveying means by the conveying means, it can be performed after the annealing step (p2), in one or more of the glass sheet cutting step (p3), the cutting step into a desired shape (p4), the chamfering step (p5), the cleaning step (p6), and the shielding layer printing step (p7) (FIG. 3), or before or after one or more of these steps. However, it is preferable to exclude the time when the shielding layer is baked in the shielding layer printing step (p7) and the time of cooling thereafter. In addition, the scratching can be performed while the glass sheet is being conveyed between one step and the following step. In particular, it is preferable to carry out the scratching treatment between the cutting step (p3) of the glass sheet and the step before the cleaning step (p6), since any glass powder that is not visible due to polishing can be removed by cleaning. The scratching treatment may be carried out at two or more timings, as long as it is carried out after the end of the annealing step (p2) and before the start of the bending step (A).
[0034] When a roller conveyor 50 (Figure 4) is used as a conveying means, the damage function of the roller conveyor can be obtained, for example, by making one or more of the rotational speed, diameter, and height of at least one of the multiple conveying rollers 51, 51, ... different from the conveying rollers adjacent to said at least one conveying roller.
[0035] For example, FIG. 7 shows a schematic cross section of an example of a roller conveyor 50 with a scratching function. As shown in FIG. 7, the angular velocity or rotational velocity (driving velocity) ω' of one conveying roller 51a can be adjusted to be larger or smaller than the angular velocity ω of the conveying roller 51 adjacent to the one conveying roller by 0.3% to 5%, preferably 0.5% to 2%. That is, the value of (|ω'-ω| / ω)×100 can be set to the ratio in the above range. In this case, it is preferable to make the angular velocity of one conveying roller larger than the angular velocity of the conveying roller adjacent to the downstream side of the one conveying roller by the ratio in the above range. Alternatively, it is preferable to make the angular velocity of one conveying roller smaller than the angular velocity of the conveying roller adjacent to the upstream side of the one conveying roller by the ratio in the above range.
[0036] The conveying rollers 51a whose angular velocities are different may be a plurality of conveying rollers arranged consecutively or discontinuously. Therefore, the angular velocity of one or more conveying rollers may be set to the angular velocity of a conveying roller adjacent to the one or more conveying rollers on the upstream side and / or the conveying roller adjacent to the one or more conveying rollers on the downstream side. corner The speed can be adjusted to be greater or less than the above ranges.
[0037] 8 is a schematic cross-sectional view of another example of a roller conveyor having a scratching function. As shown in FIG. 8, for example, the radius r' of one conveying roller 51b is determined by the radius r' of the conveying roller 51 adjacent to the one conveying roller 51b. half It can be adjusted to be larger than the diameter r by 5 μm to 2 mm, preferably 10 μm to 1 mm. In other words, it can be adjusted so that r'-r is within the above range. Here, the radii r and r' of the conveying roller are radii including the rubber body when the rubber body is arranged around the shaft body, as described above (FIGS. 5 and 6).
[0038] In the example shown in Fig. 8, it is preferable to set the radius of one conveying roller to be larger than the radius of both the conveying rollers downstream and upstream of the one conveying roller by a predetermined value. The conveying rollers 51b having different radii may be a plurality of conveying rollers arranged continuously or discontinuously. As shown in Fig. 8, the conveying rollers 51b having different radii protrude toward the glass sheet by Δr more than the adjacent conveying rollers, so that when the glass sheet passes through the conveying rollers 51b, the weight of the glass sheet is received by the conveying rollers 51b more than by the other adjacent conveying rollers 51, 51, ..., and the conveying rollers 51b rub the conveying means facing surface with a stronger force when they rotate, which can cause damage.
[0039] A similar effect can be achieved by adjusting the height (position) of one or more conveying rollers to be greater than the height of the one or more conveying rollers by 5 μm to 2 mm, preferably 10 μm to 1 mm, without changing the radius of the conveying roller.
[0040] The surface of the conveying roller can be roughened by rubbing the entire or partial surface of the conveying roller with an abrasive, abrasive paper, or the like, which can be achieved by covering the surface with a cover sheet having a rough surface. A roller conveyor (conveying means) with a scratching function can also be achieved by roughening the surface of at least one of the multiple conveying rollers, in other words, by forming irregularities on at least one surface. The degree of roughening depends on the type of glass plate to be scratched, the size and shape of the belt-shaped glass plate or glass plate, and the like, but the conveying roller can be configured to have a rough surface with an arithmetic mean roughness Ra of 0.02 μm or more and 100 μm or less as specified in JIS B 0601-2013.
[0041] The surface of the conveying roller can be roughened, for example, by rubbing the entire or part of the surface of the conveying roller with an abrasive, abrasive paper, or the like. Alternatively, it can be obtained by attaching fine powder to the surface of the conveying roller and fixing it. Alternatively, the rubber-like material on the surface that is normally used can be changed to a rubber-like material kneaded with powder for the purpose of scratching. Furthermore, it can be obtained by covering all or part of the surface of the conveying roller with a covering sheet having a rough surface. The covering sheet may be a sheet made of resin, rubber, fiber-containing material (woven fabric, knitted fabric, nonwoven fabric, paper, etc.) with a roughened surface, or a sheet having fine powder attached thereto and fixed thereon.
[0042] The sheet having the rough surface is preferably provided over a range of the conveying roller that corresponds to the entire width of the belt-shaped glass sheet or glass sheet to be scratched. In this case, it can be provided over the entire surface of the conveying roller, i.e., over the entire or almost entire axial direction of the conveying roller. The sheet having the rough surface does not have to be provided over the entire circumferential direction of the conveying roller, and can be provided, for example, by spirally winding a belt-shaped or string-shaped sheet around the surface of the conveying roller.
[0043] In the case where the conveying roller has a rubber-like body on the circumferential surface of the shaft (FIGS. 5 and 6, etc.), when the conveying roller comes into contact with the glass via a non-slippery material (rubber-like body) such as rubber attached to the conveying roller, the surface of the rubber-like body that comes into contact can be covered with a cover sheet having a rough surface. Alternatively, it can be achieved by attaching fine powder to the surface of the rubber-like body and fixing it. Furthermore, it is also possible to use a rubber-like body on the conveying roller that has abrasives such as particles kneaded into it. The cover sheet may be a sheet made of resin, rubber, fiber-containing material (woven fabric, knitted fabric, nonwoven fabric, paper, etc.) with a roughened surface, or a sheet of this type with fine powder attached and fixed to the surface.
[0044] The above-mentioned sheet with fine powder attached and fixed thereon includes a sheet with hard abrasive particles such as silica, sand, ceramics, etc., fixed thereon, such as sandpaper. When using sandpaper, the grit size may be preferably #600 or more and #15000 or less, more preferably #600 or more and #12000 or less, and even more preferably #600 or more and #8000 or less. In addition, within the above-mentioned grit size range of sandpaper, the coarser the grit size (the smaller the grit size), the better the scratching effect. However, when using sandpaper, especially when using sandpaper with a grit size of #2000 or less, it is preferable to use the sandpaper without moving it relative to the glass plate.
[0045] The scratching by the conveying means is a process performed so that the strength of the glass sheet in the plane is more uniform. Therefore, the scratching process can be said to be a process that suppresses the distribution or variation of the strength of the flat glass sheet in the plane. In other words, when the distribution of strength values (fracture stress or bending strength) measured in each of a plurality of regions in the plane of the glass sheet is obtained, the scratching process can be said to be a process that adjusts the distribution so as to narrow it. In addition, the scratching process performed in the manufacturing method of this embodiment can maintain a strength that satisfies sufficient robustness as window glass. Therefore, for example, when the surface of the glass sheet is divided into a plurality of regions and the strength of each region is measured to obtain a frequency distribution of strength, the scratching process shifts the distribution region with high strength to the direction of lower strength, and the position of the distribution region with low strength does not change much. Alternatively, the scratching process shifts the maximum value of strength to the lower side, and the minimum value of strength does not change much.
[0046] Although the effect of the scratching treatment in this embodiment may decrease somewhat when the glass sheet or laminated glass is stored for a long period of time, the effect can be maintained to a sufficient degree to ensure the bodily protection performance for a person in the event of a collision, regardless of the storage temperature and / or humidity conditions. Moreover, the effect of the scratching treatment can be similarly maintained sufficiently even when the glass sheet or laminated glass is heated to a temperature equivalent to the temperature of the heating furnace for bending.
[0047] The scratching process can be performed so that the difference between the average of the top 20% of the strength distribution of the scratched surface and the average of the top 20% of the strength distribution of the surface before scratching is 50 MPa or more, and the difference between the average of the bottom 10% of the strength distribution of the scratched surface and the average of the bottom 10% of the strength distribution of the surface before scratching is 50 MPa or less. Also, the scratching process can be performed so that the reduction rate of the average of the top 20% of the strength distribution of the surface due to scratching is 10% or more, and the reduction rate of the average of the bottom 10% of the strength distribution of the surface due to scratching is 20% or less.
[0048] Furthermore, when the distribution of strength of the surface facing the conveying means before and after the damage was obtained, the reduction rate R of the average value of the top 20% of the strength distribution of the surface facing the conveying means due to the damage was U20 is 10% or more, preferably 20% or more, and the reduction rate R of the average value of the bottom 10% of the strength distribution of the surface facing the conveying means due to the damage is L10 The damage can be made so that the damage is 20% or less, preferably 10% or less. Decrease rate R U20 (%)={(Sb U20 -Sa U20 ) / Sb U20}×100 Sb U20 : Average value of the top 20% of the strength distribution on the surface facing the conveyor before damage Sa U20 : Average value of the top 20% of the strength distribution on the surface facing the conveyor after damage Decrease rate R L10 (%)={(Sb L10 -Sa L10 ) / Sb L10}×10 0 Sb L10 : Average value of the bottom 10% of the strength distribution on the surface facing the conveyor before damage Sa L10 : Average value of the bottom 10% of the strength distribution on the surface facing the conveyor after damage It is.
[0049] The method for measuring the above strength is not particularly limited as long as the measurement conditions are the same before and after the scratching, but it can be measured and calculated using the method using R30 described in ISO1288-5 (2016) described below.
[0050] In this way, the damage processing in this embodiment can be performed so that the average value of the top 20% or more of the intensity distribution is significantly reduced, i.e., so that the areas of excessively high intensity are reduced, and the average value of the bottom 10% or less of the intensity distribution, i.e., the intensity of the low-intensity areas, is not excessively low or the number of such areas is not excessively increased.
[0051] Furthermore, when the distribution of strength of the surface facing the conveying means before and after the damage was obtained, the average of the top 20% of the strength distribution of the surface facing the conveying means before the damage (Sb U20 ) and the average of the top 20% of the strength distribution on the surface facing the conveying means after damage (Sa U20 ) and the difference (Sb U20 -Sa U20 ) is 50 MPa or more, preferably 70 MPa or more, and the average (Sb L10 ) of the bottom 10% of the strength distribution on the surface facing the conveyor after damage (Sa L10 ) and the difference (Sb L10 -Sa L10 ) is 50 MPa or less, preferably 30 MPa or less. In this case, the strength can be the breaking stress measured by the method using R30 described in ISO1288-5 (2016).
[0052] In addition, when the strength distribution was calculated for the surface of the damaged glass sheet facing the conveying means and the non-facing surface (F2 in FIG. 4) that was not damaged on the opposite side of the surface facing the conveying means, the average of the top 20% of the strength distribution on the non-facing surface (Sn U20 ) and the average of the top 20% of the strength distribution on the conveying means surface (Sf U20 ) and the difference (Sn U20 -Science fiction U20 ) is 50 MPa or more, preferably 70 MPa or more, and the average (Sn L10) and the average of the bottom 10% of the strength distribution on the conveying means surface (Sf L10 ) and the difference (Sn L10 -Science fiction L10 ) is 50 MPa or less, preferably 30 MPa or less. In this case, the strength can be the breaking stress measured by the method using R30 described in ISO1288-5 (2016).
[0053] In the method described in ISO1288-5(2016), a glass plate to be tested is placed on a support ring having a predetermined diameter, and a load is gradually increased from above the support ring using a load ring having a predetermined diameter smaller than the support ring, and the load at the time of breakage is measured. The load is applied from the opposite side of the surface to which the strength is to be determined. Then, from the obtained measured value, a fracture stress value is obtained based on a predetermined formula described in ISO1288-5(2016). Here, in order to obtain the strength distribution within the surface, the glass plate is cut and divided into a predetermined size, and the fracture stress can be measured for each divided area. In this case, the size of the glass after division (cutting out) is not particularly limited, but may be 60 mm to 300 mm x 60 mm to 300 mm. In addition, the number of divided samples for obtaining the strength distribution may be preferably 30 or more, more preferably 50 or more. In addition, when the measurement target is not a flat plate but a curved glass plate or laminated glass, the fracture stress of the curved area cut out is measured. In such cases, the measurement and calculation does not use the specified formula described in the ISO, but an approximate formula is derived from stress measurements, and the breaking stress value can be obtained by substituting the measured value into the approximate formula.
[0054] The scratching by the conveying means described above can also be performed by interposing water or an aqueous solution between the conveying means and the surface of the glass plate facing the conveying means. The water or aqueous solution can be applied, spread, or sprayed onto the surface of the conveying means before scratching. However, when scratching is performed in the cleaning step (step 6 in FIG. 3, or cleaning other than step 6), there is no need to add water or an aqueous solution since the cleaning liquid (including the detergent liquid and the rinsing liquid) is interposed between the glass plate and the conveying means.
[0055] As shown in Fig. 3, in this embodiment, the bending process (A) is performed after the preparation process (p) including the damage caused by the conveying means as described above. This bending process (A) is a process of bending a flat glass sheet by heating it to near its softening point or above its softening point. This bending process may be gravity bending, in which the glass sheet is placed on a ring mold and bent by its own weight in a heating furnace, or press bending, in which the glass sheet is sandwiched and pressed between a ring mold (lower mold) and a press mold (upper mold), or a combination of these.
[0056] In the bending process (A), a glass sheet may be bent independently, or two glass sheets to be bonded in the subsequent laminating process (B) may be stacked and bent in the stacked state. In either case, the glass sheet is often curved so as to be convex downward (vertically downward). Here, in the flat glass sheet preparation process (p), as described above, at least one of the two glass sheets is scratched on the conveying means facing surface (facing downward). On the other hand, in the curved laminated glass used for windshields, etc., it is preferable that the surface (second surface 12 and / or fourth surface 22) on the vehicle interior side, which is a concave surface, is scratched. Therefore, in the case where the glass sheet is formed in a horizontally placed state, in the method according to this embodiment, it is preferable to turn over the scratched glass sheet after the scratching process by the conveying means in the preparation process (p). As a result, if the scratched surface faces the vertically upward side and is sent to the bending process (A) and bent in this orientation, a glass sheet with a scratching process on the concave surface is obtained.
[0057] The heating temperature of the glass during bending may be about 550°C or more and 700°C or less. The bending process (A) may be a single-bend bending process in which a flat glass sheet is bent in only one direction, for example, only in the left-right direction or the up-down direction of the automobile when the glass sheet is attached to an opening of the automobile, or a compound-bend bending process in which the glass sheet is bent in both the left-right direction and the up-down direction. The curvature radius of the glass sheet obtained by the bending process (A) may be 200 mm or more and 30,000 mm or less. The curvature radius of the exterior glass sheet 10 and the interior glass sheet 20 in the laminated glass for automobile windows 1 may be the same or different. The effect of the above-mentioned scratching treatment of this embodiment can be maintained even after the heating during the above-mentioned bending process.
[0058] The laminating step (B) is a step of bonding two glass sheets bent in the bending step (A) via an intermediate film to obtain a laminated glass. In the laminating step (B), the glass sheets are laminated so that the surface of the glass sheets facing the conveying means when scratched in the preparation step (p) becomes the surface facing the inside of the vehicle when the glass sheets are mounted on the vehicle, and the two glass sheets are bonded together. The laminating step (B) may include a step of sandwiching the above-mentioned resin intermediate film between two glass sheets to form a laminate, placing the laminate in a rubber bag and heating it under reduced pressure to perform a degassing treatment, and then heating and pressurizing the laminate in an autoclave to perform a main bonding step. The preliminary bonding step may be a rubber channel method or a nip roller method.
[0059] Embodiment B Next, a method for producing laminated glass for automobile windows according to embodiment b, which is another embodiment of the present invention, will be described. Fig. 9 shows a flow diagram of one example of a method for producing laminated glass for automobile windows according to this embodiment. As shown in Fig. 9, the production method of this embodiment includes a step (A) of bending a flat glass sheet, and a step (B) of laminating two bent glass sheets together. This production method also includes a step (p) of preparing a flat glass sheet to be subjected to the bending step (A) as a pre-step of the bending step (A).
[0060] As shown in FIG. 9, the flat glass sheet preparation step (p) may include manufacturing a long belt-shaped glass sheet by a float method, a roll-out method, or the like (p1), annealing the belt-shaped glass sheet (p2), cutting out a blank sheet from the belt-shaped glass sheet (p3), cutting the blank sheet into a desired shape (p4), chamfering (p5), cleaning (p6), and printing a shielding layer (p7). These steps p1 to p7 are only an example, and the order of each step p1 to p7 may be partially changed. In addition, some of these steps may be changed or omitted, and additional steps other than steps p1 to p7 may be included at any timing of steps p1 to p7. For example, one or more additional cleaning steps other than the cleaning step (p6) may be added at any timing after the end of the annealing step (p2) and before the chamfering (p5).
[0061] Conventionally, various safety-related properties and functions have been required for laminated glass for automobile windows, but the requirements are becoming greater. In particular, in recent years, importance has been attached not only to the viewpoint of passenger protection but also to the viewpoint of protecting the body of pedestrians (pedestrians, cyclists, etc.) when they collide. Laminated glass for automobile windows is also required to satisfy specific standards such as the Head Injury Criterion (HIC), on the premise that it has appropriate robustness as automobile window glass. For example, a HIC value of less than 1,000, preferably less than 650, may be required in a specific region of laminated glass for automobile windows. Here, in order to improve the body protection performance of pedestrians, etc. in the event of a collision, it is important that the region (high strength region) in laminated glass for automobile windows with excessively high strength is reduced or eliminated, and the distribution of strength over the surface direction is suppressed (the strength distribution is narrowed), that is, the strength within the surface is made as uniform or level as possible.
[0062] In contrast, the manufacturing method of laminated glass for automobile windows according to this embodiment includes scratching the surface of a flat glass sheet before the bending process (A). In this specification, "scratching" refers to a process of forming fine cracks (also called microcracks, which are fine cracks on the order of micrometers or less that cannot be visually recognized) on the surface of the glass sheet. In this embodiment, scratching the surface of the glass sheet can make the strength of the glass sheet and the laminated glass obtained using the glass sheet uniform or level across the surface. Originally, fine cracks exist on the surface of the glass sheet after production, and it is said that the uneven distribution of these fine cracks is the cause of the variation in strength of glass for automobile windows. However, according to the manufacturing method according to this embodiment, it is considered that the strength of the region where the strength is excessively high (high strength region) can be reduced by introducing new fine cracks into the surface of the glass sheet by scratching. On the other hand, scratching in this embodiment is a process that does not further reduce the strength of the region where the strength is relatively low (low strength region), or hardly reduces it at all. Therefore, by carrying out the scratching treatment in this embodiment, the strength of the glass sheet or the obtained laminated glass can be made uniform within the plane, and the strength required for automobile window glass can be maintained. As a result, it is possible to provide an automobile window laminated glass that has the robustness required for automobile window glass and also has the performance to ensure the physical safety of pedestrians and the like in the event of a collision with the pedestrians and the like.
[0063] In this embodiment, the scratching treatment is performed on at least one of the two flat glass sheets that form the laminated glass, the surface that faces the inside of the vehicle when the laminated glass is attached to the vehicle. For example, when a pedestrian or the like collides with the windshield of the vehicle from the outside of the vehicle, the impact of the collision is transmitted in sequence from the first surface 11 of the exterior glass sheet 10, which is the outermost surface, to the fourth surface 22 (FIG. 2) of the interior glass sheet 20, which is the innermost surface. At this time, in the exterior glass sheet 10, a compressive stress against a compressive force that contracts the area occurs on the first surface 11, and conversely, a tensile stress against a tensile force that expands the area occurs on the second surface 12, so that the exterior glass sheet 10 is likely to start cracking from the second surface 12 on the inside of the vehicle. For this reason, it is preferable that the second surface 12 is appropriately susceptible to cracking upon collision, that is, there is no or little high-strength region in which the strength is excessively high locally on the second surface 12. Similarly, when focusing on the interior glass sheet 20, a compressive stress against a compressive force that contracts the area occurs in the third surface 21, and a tensile stress against a tensile force that expands the area occurs in the fourth surface 22, so that the interior glass sheet 20 is likely to start cracking from the fourth surface 22 on the interior side of the vehicle. Therefore, it is preferable that the fourth surface 22 is appropriately susceptible to cracking during a collision, that is, there is no or little high-strength area in which the strength is excessively high locally in the fourth surface 22. Therefore, in this embodiment, from the viewpoint of protecting the bodies of pedestrians and the like during a collision, at least one of the second surface 12 on the interior side of the exterior glass sheet 10 and the fourth surface 22 on the interior side of the interior glass sheet 20 is scratched. Furthermore, if only one of the second surface 12 and the fourth surface 22 is to be scratched, it is more preferable to scratch the second surface 12, which is more affected by the impact during a collision, and it is even more preferable to scratch both the second surface 12 and the fourth surface 22.
[0064] The glass plate to which the scratching process is applied in this embodiment is in a flat state before being bent. That is, the scratching process is applied to the flat surface of the glass plate, not to the curved surface of the glass plate. The scratching process is preferably applied to the entire surface of the glass plate in order to make the strength in the surface more uniform. However, if the scratching process is applied to the curved surface of the glass body evenly, it becomes necessary to change the direction in which the scratching means faces or the scratching means itself according to the curve of the curved surface, which tends to make the process complicated. Furthermore, in this embodiment, the scratching process is applied to at least one of the second surface 12 and the fourth surface 22 as described above, which will be the surface on the inside of the vehicle when the laminated glass is obtained in the subsequent lamination process (B), but the surface on the inside of the vehicle is a concave surface (FIG. 2). And, when trying to process the concave surface, it is even more difficult to perform scratching according to the curve of the curved surface, which tends to limit the configuration of the scratching means. Therefore, scratching the concave surface may result in an area that is not scratched, leaving a high-strength area, or conversely, the concave surface may be scratched so that the strength is excessively reduced and the required robustness cannot be obtained. In contrast, scratching the flat surface of a glass plate is relatively easy since there is no need to take into account the curvature of the surface, and the effort and cost required to configure scratching means can be reduced.
[0065] In the present manufacturing method, the scratching is performed in the step (p) of preparing a flat glass sheet, but can be performed at any timing after the above-mentioned annealing step (p2) and before the bending step (A). More specifically, the scratching can be performed after the annealing step (p2), in one or more of the steps of cutting out the glass sheet (p3), cutting into a desired shape (p4), chamfering (p5), cleaning (p6), and shielding layer printing (p7) (FIG. 9), or before or after one or more of these steps. However, it is preferable to exclude the cooling of the shielding layer after the shielding layer printing step (p7). The scratching can be preferably performed on the glass sheet after the step (p4) of cutting the blank into a desired shape. This allows the scratched area to be cut off, that is, the scratching can be performed over the entire surface of the glass sheet with the desired shape without waste. Moreover, the scratching treatment may be carried out at two or more timings, as long as it is carried out after the end of the slow cooling step (p2) and before the start of the bending step (A).
[0066] When mass-producing laminated glass, a line production method in which processing devices for performing a plurality of steps as described above are installed in a row is preferably used. In this case, the belt-shaped glass sheet or glass sheet is transported by a transporting means between processing devices and / or within one or more processing devices. As the transporting means, a transporting means that supports and transports the belt-shaped glass sheet or glass sheet from below is preferable because it has a simple structure and can transport safely and with less damage. Specific examples of the transporting means include a roll conveyor and a belt conveyor (including a flat belt conveyor and a round belt conveyor). Here, the scratching in this embodiment is performed on the side opposite to the transporting means. That is, the surface (referred to as a non-facing surface) opposite to the surface (referred to as a surface facing the transporting means) of the flat glass sheet is scratched. When the transporting means is a transporting means that supports and transports the glass sheet from below, the upper surface of the glass sheet is the non-facing surface. In this manner, it is preferable that the non-opposing surface faces upward, i.e., the surface to be scratched faces upward, in that it is easy to check the progress of the scratching treatment and the state of the glass sheet after the scratching treatment.
[0067] In this embodiment, the scratching can be performed, for example, by contacting the scratching tool with the non-opposing surface of the flat glass plate and moving it relative to the non-opposing surface. The shape of the scratching tool is not particularly limited, and may be a brush, a paintbrush, a roller, a film or sheet, a blade, a disk, or the like. Thus, the scratching tool may be one whose contact point with the surface of the glass plate is flat, or one whose contact point with the surface of the glass plate is discontinuous (such as a brush in which the tips of multiple bristles contact the non-opposing surface). The material of the scratching tool may be ceramics, metal, synthetic resin (plastic), natural material, or the like. It may also be a foam such as a foamed resin molded product. In the case of a scratching tool that contacts the surface of the glass plate on a flat surface, it may be in the form of a resin sheet molded by extrusion molding, or may be a fiber structure molded by assembling fibers three-dimensionally or two-dimensionally, and may be felt, cloth (including woven fabric and knitted fabric), nonwoven fabric, paper, or the like. In addition, when the wounding tool is made of resin or contains resin as a material of the wounding tool, specific examples of the resin include ultra-low density polyethylene, linear low density polyethylene, low density polyethylene, high density polyethylene, polypropylene, polystyrene, polyurethane, silicone resin, EVA, and olefin-based elastomer. The tool may be made of any of the above materials alone or in combination of two or more kinds.
[0068] At least the part of the surface of the tool that is to come into contact with the glass plate may be smooth, or may have fine irregularities formed such that the arithmetic mean roughness (surface roughness) Ra defined in JIS B 0601-2013 is 0.02 μm or more and 100 μm or less. Such fine irregularities on the surface of the tool may be inherent to the material (such as irregularities formed by the arrangement of fibers in a fiber structure). In addition, at least the part of the surface of the tool that is to come into contact with the glass plate may be roughened, or may be formed by attaching and fixing fine powder, or by kneading powder during molding of a material such as resin. In addition, in the case of fibers or cloth made of twisted or woven bundled fibers, irregularities formed by the bundled fibers, etc., are formed, and these may be present.
[0069] The tool for scratching (scratching tool) may be a sheet to which fine powder as described above is attached and fixed. Such sheets include sheets to which hard abrasive particles such as silica, sand, and ceramics are fixed, such as sandpaper. When sandpaper is used, its grit size may be preferably #600 or more and #15000 or less, more preferably #600 or more and #12000 or less, and even more preferably #600 or more and #8000 or less. In addition, within the above-mentioned grit size range of sandpaper, the coarser the grit (the smaller the grit size), the better the scratching effect. However, when sandpaper is used, particularly when sandpaper of #2000 or less is used, it is preferable to use the sandpaper without moving it relative to the glass plate.
[0070] When using a sheet with fine powder attached and fixed as described above, the surface of the sheet with the powder attached thereto can be placed facing the surface to be scratched (the non-opposing surface in the case of embodiment b), and a load can be applied from above. The means for applying the load is not particularly limited, but from the viewpoint of applying a more uniform load over the entire surface of the glass plate, it is preferable to use a roller. For example, a roller can be rolled from above the sheet on the side of the glass plate on which the sheet (scratching tool) is placed, or pressure can be applied from both sides of the glass plate by passing the glass plate between a pair of rollers. Alternatively, a roller can be prepared around which the sheet (scratching tool) is wrapped so that the rough surface (the surface on which the fine powder is fixed) is exposed, and such a roller can be rolled in contact with the surface to be scratched. Furthermore, scratching can be performed by passing the glass plate between a roller around which a sheet with fine powder attached is wrapped and a roller facing the roller.
[0071] In addition, an abrasive may be used for scratching. In this specification, the abrasive refers to a powder having an abrasive action with fluidity, which can be scattered or dispersed in a solvent. By using the abrasive, even a scratching tool that does not have a minute unevenness formed on the surface can easily perform scratching. When using an abrasive, the abrasive is scattered on the non-opposing surface of the flat glass plate, and then the non-opposing surface can be rubbed by wiping or sweeping with the scratching tool. At that time, the scratching tool can be moved relative to the glass plate along the surface of the glass plate with or without applying a pressing force. The abrasive may be a powder in a dry state, a powder moistened with a liquid, or a slurry or liquid in which the powder is dispersed in a liquid. In this case, the liquid is not particularly limited as long as it does not modify the surface of the glass plate, and may be one or more of water, an aqueous solution, and an organic solvent, and the liquid may be volatile or non-volatile. In the case of a slurry or liquid abrasive, the liquid abrasive may be prepared in advance by mixing the powder with an aqueous liquid, or during the scratching process, the powder may be sprayed onto the surface of the glass plate and then the liquid, or the liquid may be sprayed and then the powder, and then the scratching tool may be brought into contact with the surface to perform the scratching process.
[0072] Thus, in this embodiment, an abrasive containing a liquid such as water or an aqueous solution can be used, or a powdered abrasive can be added with a liquid such as water or an aqueous solution to perform scratching. That is, when scratching, a liquid such as water or an aqueous solution can be interposed between the scratching tool and the non-facing surface of the glass plate. In this way, the presence of a liquid, particularly water, can prevent a temperature rise that may occur due to the rubbing of the scratching tool, prevent the scattering of powder contained in the abrasive or fine chips from the glass plate, and facilitate chemical polishing. Therefore, when scratching is performed in or after the cleaning step (step p6 in FIG. 9 or any cleaning performed at a timing other than step p6), the water used in the cleaning step can be used, which is preferable.
[0073] The powder used in the abrasive for scratching may contain an inorganic material or an organic material, or both, but it is preferable that the powder is an inorganic powder. Examples of inorganic powders include cerium oxide, glass beads, titanium oxide, diamond, calcium carbonate, anhydrous silicic acid, sodium hydrogen phosphate, silicon nitride, silicon carbide, aluminum oxide, etc. Among these, cerium oxide is preferable because of its high hardness and its polishing aiding effect due to chemical reaction with glass. These powders can be used alone or in combination of two or more. The median diameter (D50) of the powder used, measured by the method (wet) described in JIS Z 8825:2013, may be preferably 0.1 μm or more and 100 μm or less, more preferably 0.2 μm or more and 30 μm or less, and even more preferably 0.2 μm or more and 15 μm or less. When the powder particle size (median diameter) is 0.1 μm or more, the polishing effect can be improved and the uniformity of the in-plane strength distribution can be promoted, and when the powder particle size is 100 μm or less, the occurrence of visible scratches can be avoided and the required robustness of the glass plate or the resulting laminated glass can be prevented from being impaired.
[0074] When an abrasive is used, after the non-facing surface of the glass plate is polished using the scratching tool, the abrasive can be removed. For example, cleaning can be performed by spraying or pouring a liquid such as water or an organic solvent. In this case, a tool similar to the scratching tool can be used. Note that when scratching is performed at a stage prior to the cleaning step (step p6 in FIG. 9 or any cleaning performed at a timing other than step p6), the abrasive can be removed by the cleaning step, so the work of removing the abrasive can be omitted.
[0075] When the scratching tool is moved relative to the glass plate, the scratching tool can be moved in any direction on the non-opposing surface of the glass plate. The movement may be a one-way movement in one direction, a reciprocating movement in a predetermined direction, a rotational movement, or a combination of these. When the scratching tool is moved, the scratching tool can be moved with a predetermined pressing force on the surface of the glass plate, or without or substantially without applying a pressing force. The scratching tool may be connected to a drive unit such as an electric motor and a control unit, which allows the scraping speed, pressing force, etc. to be controlled.
[0076] The speed at which the scratching tool rubs the surface of the glass plate may be 1 mm / sec or more and 6 m / sec or less. Furthermore, when an abrasive is used and the surface of the scratching tool that contacts the non-facing surface of the glass plate is smooth, the speed at which the scratching tool rubs the surface of the glass plate may be preferably 10 mm / sec or more and 3 m / sec or less, more preferably 20 mm / sec or more and 2 m / sec or less. On the other hand, when an abrasive is not used and the surface of the scratching tool that contacts the non-facing surface of the glass plate is uneven, the speed at which the scratching tool rubs the surface of the glass plate may be preferably 1 mm / sec or more and 1 m / sec or less, more preferably 2 mm / sec or more and 50 cm / sec or less.
[0077] Furthermore, the scratching means for scratching the glass sheet may be a non-contact means, not a scratching tool that comes into contact with the surface of the glass sheet as described above. For example, scratching can be performed using a means for applying electromagnetic energy, thermal energy, light energy, etc., and for example, plasma treatment, corona treatment, laser irradiation, etc. can be used.
[0078] FIG. 10 shows a specific example of the scratching means in the embodiment b. FIG. 10 shows, as an example, a state in which scratching is performed at the timing after a flat glass plate (raw plate) is cut out from a belt-shaped glass plate (step p3). In the example shown in FIG. 10, the cut flat glass plates G, G, ... are supported from below by a flat belt conveyor (conveying means) 50 and conveyed in a conveying direction Dt. Then, a scratching means 60 is installed in the middle of the conveying direction Dt, and the scratching means 60 scratches the opposing surface F2 of the flat glass plates G, G, ... on the opposite side to the surface facing the conveying means 50. In the example of FIG. 10, the scratching means 60 may be a polishing machine (grinder) equipped with a rotatable disc-shaped polishing pad 61. When the scratching means 60 is a polishing machine, the polishing pad 61 may be configured to be capable of rotation, revolution, and both of rotational motion, or may be configured to be capable of reciprocating motion.
[0079] The scratching process on the non-opposing surface of the flat glass plate described above with a specific example can make the strength of the glass plate uniform. Therefore, the scratching process can be said to be a process that suppresses the distribution or variation of the strength of the flat glass plate. In other words, when the distribution of strength values (fracture stress or bending strength) measured in a plurality of regions in the plane of the glass plate is obtained, the scratching process can be said to be a process that adjusts the distribution so as to narrow it. In addition, the scratching process performed in the manufacturing method of this embodiment can maintain a strength that satisfies sufficient robustness as a window glass. Therefore, for example, when the surface of the glass plate is divided into a plurality of regions, the strength of each region is measured, and a frequency distribution of the strength is obtained, the scratching process shifts the distribution region with high strength to the direction of low strength, and the position of the distribution region with low strength does not change much. Alternatively, the scratching process shifts the maximum value of the strength to the lower side, and the minimum value of the strength does not change much.
[0080] Although the effect of the scratching treatment in this embodiment may decrease somewhat when the glass sheet or laminated glass is stored for a long period of time, the effect can be maintained to a sufficient degree to ensure the bodily protection performance for a person in the event of a collision, regardless of the storage temperature and / or humidity conditions. Moreover, the effect of the scratching treatment can be similarly maintained sufficiently even when the glass sheet or laminated glass is heated to a temperature equivalent to the temperature of the heating furnace for bending.
[0081] The scratching process can be performed so that the difference between the average of the top 20% of the strength distribution of the scratched surface and the average of the top 20% of the strength distribution of the surface before scratching is 50 MPa or more, and the difference between the average of the bottom 10% of the strength distribution of the scratched surface and the average of the bottom 10% of the strength distribution of the surface before scratching is 50 MPa or less. Also, the scratching process can be performed so that the reduction rate of the average of the top 20% of the strength distribution of the surface due to scratching is 10% or more, and the reduction rate of the average of the bottom 10% of the strength distribution of the surface due to scratching is 20% or less.
[0082] Furthermore, when the distribution of strength of the treated surface or scratched surface (non-facing surface) of the glass plate before and after scratching is obtained, the reduction rate R of the average value of the top 20% of the strength distribution of the non-facing surface due to scratching is U20 is 10% or more, preferably 20% or more, and the reduction rate R of the average value of the bottom 10% of the strength distribution of the non-opposing surface due to the damage is L10 The damage can be made so that the damage is 20% or less, preferably 10% or less. Decrease rate R U20 (%)={(Sb U20 -Sa U20 ) / Sb U20}×100 Sb U20 : Average value of the top 20% of the strength distribution on the non-facing surface before damage Sa U20 : Average value of the top 20% of the strength distribution on the non-facing surface after damage Decrease rate R L10 (%)={(Sb L10 -Sa L10 ) / Sb L10}×10 0 Sb L10: Average value of the bottom 10% of the strength distribution on the non-facing surface before damage Sa L10 : Average value of the bottom 10% of the strength distribution on the non-facing surface after damage The method for measuring the above strength is not particularly limited as long as the measurement conditions are the same before and after the scratching, but it can be measured and calculated by the method using R30 described in ISO1288-5 (2016) described later.
[0083] In this way, the damage processing in this embodiment can be performed so that the average value of the top 20% or more of the intensity distribution is significantly reduced, i.e., so that the areas of excessively high intensity are reduced, and the average value of the bottom 10% or less of the intensity distribution, i.e., the intensity of the low-intensity areas, is not excessively low or the number of such areas is not excessively increased.
[0084] Furthermore, when the distribution of strength of the treated surface or the scratched surface (non-opposing surface) before and after scratching was obtained, the average of the top 20% of the strength distribution of the treated surface or the scratched surface before scratching (Sb U20 ) and the average of the top 20% of the strength distribution of the treated or scratched surface after scratching (Sa U20 ) and the difference (Sb U20 -Sa U20 ) is 50 MPa or more, preferably 70 MPa or more, and the average (Sb L10 ) of the bottom 10% of the strength distribution of the treated or scratched surface after scratching (Sa L10 ) and the difference (Sb L10 -Sa L10 ) is 50 MPa or less, preferably 30 MPa or less. In this case, the strength can be the breaking stress measured by the method using R30 described in ISO1288-5 (2016).
[0085] In addition, when the distribution of strength is determined for the treated or scratched surface of the scratched glass sheet, that is, the non-facing surface which is the surface opposite to the conveying means facing surface in this embodiment, and the conveying means facing surface which is the untreated or non-scratched surface, the average (SfU20 ) and the average of the top 20% of the strength distribution on the non-opposing surface (treated surface) (Sn U20 ) and the difference (Sf U20 -Sn U20 ) is 50 MPa or more, preferably 70 MPa or more, and the average (Sf L10 ) and the average of the bottom 10% of the strength distribution on the non-opposing surface (treated surface) (Sn L10 ) and the difference (Sf L10 -Sn L10 ) is 50 MPa or less, preferably 30 MPa or less. In this case, the strength can be the breaking stress measured by the method using R30 described in ISO1288-5 (2016).
[0086] In the method described in ISO1288-5(2016), a glass plate to be tested is placed on a support ring having a predetermined diameter, and a load is gradually increased from above the support ring using a load ring having a predetermined diameter smaller than the support ring, and the load at the time of breakage is measured. The load is applied from the opposite side of the surface to which the strength is to be determined. Then, from the obtained measured value, a fracture stress value is obtained based on a predetermined formula described in ISO1288-5(2016). Here, in order to obtain the strength distribution within the surface, the glass plate is cut and divided into a predetermined size, and the fracture stress can be measured for each divided area. In this case, the size of the glass after division (cutting out) is not particularly limited, but may be 60 mm to 300 mm x 60 mm to 300 mm. In addition, the number of divided samples for obtaining the strength distribution may be preferably 30 or more, more preferably 50 or more. In addition, when the measurement target is not a flat plate but a curved glass plate or laminated glass, the fracture stress of the curved area cut out is measured. In such cases, the measurement and calculation does not use the specified formula described in the ISO, but an approximate formula is derived from stress measurements, and the breaking stress value can be obtained by substituting the measured value into the approximate formula.
[0087] As shown in Fig. 9, in this embodiment, a flat glass sheet obtained through a preparation step (p) including scratching is subjected to a bending step (A). This bending step (A) is a step of bending a flat glass sheet by heating it to near its softening point or above its softening point. The bending may be gravity bending in which the glass sheet is placed on a ring mold and bent by its own weight in a heating furnace, or press bending in which the glass sheet is sandwiched and pressed between a ring mold (lower mold) and a press mold (upper mold), or a combination thereof.
[0088] In the bending process (A), a glass sheet may be bent independently, or two glass sheets to be bonded in the subsequent laminating process (B) may be stacked and bent in the stacked state. In either case, the glass sheet is often curved so as to be convex downward (vertically downward). Here, in the flat glass sheet preparation process (p) in this embodiment, as described above, the non-facing surface (upward surface) of at least one of the two glass sheets opposite to the conveying means facing surface is scratched. On the other hand, in curved laminated glass used for windshields, etc., it is preferable that the surface (second surface 12 and / or fourth surface 22) on the vehicle interior side, which is a concave surface, is scratched. In this case, in the method according to this embodiment, after the scratching process is performed in the preparation process (p), the glass sheet with the upper surface scratched is transported, so that the glass sheet can be transferred to the bending process (A) without being turned over. A glass sheet having an upper surface scratched is bent in a normal manner so as to have a convex shape on the lower side, thereby obtaining a glass sheet having a concave surface scratched.
[0089] The heating temperature of the glass during bending may be about 550°C or more and 700°C or less. The bending process (A) may be a single-bend bending process in which a flat glass sheet is bent in only one direction, for example, only in the left-right direction or the up-down direction of the automobile when the glass sheet is attached to an opening of the automobile, or a compound-bend bending process in which the glass sheet is bent in both the left-right direction and the up-down direction. The curvature radius of the glass sheet obtained by the bending process (A) may be 200 mm or more and 30,000 mm or less. The curvature radius of the exterior glass sheet 10 and the interior glass sheet 20 in the laminated glass for automobile windows 1 may be the same or different. The effect of the above-mentioned scratching treatment in this embodiment can be maintained even after the heating during the above-mentioned bending process.
[0090] The laminating step (B) is a step of bonding two glass sheets bent in the bending step (A) via an intermediate film to obtain a laminated glass. In the laminating step (B), the glass sheets are laminated so that the surface of the glass sheets that was scratched in the preparation step (p) (the surface opposite to the surface facing the conveying means) faces the inside of the vehicle when the glass sheets are attached to the vehicle, and the two glass sheets are bonded together. The laminating step (B) may include a step of sandwiching the above-mentioned resin intermediate film between two glass sheets to form a laminate, placing the laminate in a rubber bag and heating it under reduced pressure to perform a degassing treatment, and then heating and pressurizing the laminate in an autoclave to perform a main bonding step. The preliminary bonding step may be a rubber channel method or a nip roller method.
[0091] <Laminated glass for automobile windows> Another embodiment of the present invention is a laminated glass for automobile windows formed by bonding an exterior glass plate 10 and an interior glass plate 20 via an intermediate film 30, in which when the exterior side of the exterior glass plate 10 is designated as a first side 11, the interior side thereof is designated as a second side 12, and the exterior side of the interior glass plate 20 is designated as a third side 21 and the interior side thereof is designated as a fourth side 22 (Figure 2), the laminated glass may satisfy one or more of the following conditions 1 to 3.
[0092] Condition 1: The average value of the top 20% of the intensity distribution on the first surface 11 (S1 U20 ) and the average value of the top 20% of the intensity distribution of the fourth surface 22 (S4U20 ) and the difference (S1 U20 -S4 U20 ) is 50 MPa or more, preferably 70 MPa or more, and the average value (S1 L10 ) and the average value of the bottom 10% of the intensity distribution of the fourth surface 22 (S4 L10 ) and the difference (S1 L10 -S4 L10 ) is 50 MPa or less, preferably 30 MPa or less. Condition 2: The average value of the top 20% of the intensity distribution on the first surface 11 (S1 U20 ) and the average value of the top 20% of the intensity distribution on the second surface 12 (S2 U20 ) and the difference (S1 U20 -S2 U20 ) is 50 MPa or more, preferably 70 MPa or more, and the average value (S1 L10 ) and the average value of the bottom 10% of the intensity distribution on the second surface 12 (S2 L10 ) and the difference (S1 L10 -S2 L10 ) is 50 MPa or less, preferably 30 MPa or less. Condition 3: The average value of the top 20% of the intensity distribution on the third surface 21 (S3 U20 ) and the average value of the top 20% of the intensity distribution of the fourth surface 22 (S4 U20 ) and the difference (S3 U20 -S4 U20 ) is 50 MPa or more, preferably 70 MPa or more, and the average value (S3 L10 ) and the average value of the bottom 10% of the intensity distribution of the fourth surface 22 (S4 L10 ) and the difference (S3 L10 -S4 L10 ) is 50 MPa or less, preferably 30 MPa or less.
[0093] The strengths under Conditions 1 to 3 above may be fracture stresses measured by a method conforming to ISO1288-5 (2016) by applying a load from the surface opposite to the surface for which the strength distribution is to be obtained. When measuring the strengths of the second surface 12 on the interior side of the exterior glass sheet 10 and the fourth surface 22 of the interior glass sheet 20, the exterior glass sheet 10 and the interior glass sheet 20 can be separated from each other in a laminated glass state and the interlayer 30 removed before measurement. Of the measurements performed under Conditions 1 to 3 above, when determining the value under Condition 1, the strength can be measured without destroying the laminated glass structure.
[0094] By satisfying one or more of the above conditions 1 to 3, it is possible to obtain a laminated glass in which both areas with excessively high strength and areas with excessively low strength are reduced or eliminated within at least one of the second surface 12 and the fourth surface 22, that is, a laminated glass in which the strength within the surface is uniform and which also has sufficient strength as window glass. Therefore, according to this embodiment, it is possible to provide a laminated glass for automobile windows which can appropriately break and absorb the impact when it receives an impact from outside the vehicle, thereby ensuring the physical protection performance of pedestrians, etc. even when a pedestrian, etc., is hit from outside the vehicle, and which also has sufficient robustness as an automobile window glass.
[0095] Among the above conditions 1 to 3, it is preferable that at least condition 2 is satisfied. When condition 2 is satisfied, the strength of the second surface 12, which is most susceptible to impact when the laminated glass receives an impact from outside the vehicle, is uniformized, and areas with excessively high strength are reduced or eliminated. This allows the laminated glass to break appropriately and improves the impact absorption effect, thereby further improving the body protection performance of pedestrians and the like in the event of a collision with a pedestrian and the like.
[0096] The laminated glass for automobile windows according to this embodiment may be a laminated glass for automobile windows 1 (FIG. 2) in which an exterior glass sheet 10 and an interior glass sheet 20 are joined via an interlayer 30, and the average value of the top 20% of the fracture stress distribution in the transmission region, measured by a method conforming to ISO1288-5 (2016) while applying a load from the exterior of the vehicle, is 500 MPa or less, preferably 450 MPa or less. In this specification, the transmission region refers to the portion of the laminated glass for automobile windows excluding the shielding layer formed on the laminated glass for automobile windows.
[0097] The laminated glass for automobile windows according to this embodiment may be one in which at least one of the second surface 12 on the vehicle interior side of the exterior glass sheet 10 and the fourth surface 22 on the vehicle exterior side of the interior glass sheet 20 is scratched as explained by the above-mentioned manufacturing method for laminated glass for automobile windows. That is, the laminated glass for automobile windows according to this embodiment may be a laminated glass manufactured by a manufacturing method including a step (A) of heating and bending two glass sheets and a step (B) of bonding the two bent glass sheets together via an interlayer film, and may be obtained by conveying at least one of two flat glass sheets by a conveying means before the step (A), scratching a surface of the at least one glass sheet facing the conveying means or a non-facing surface opposite to the surface facing the conveying means, bending the two glass sheets (A), bonding the two bent glass sheets together via an interlayer film (B), and arranging the scratched surface to face the vehicle interior side when the laminated glass is attached to an opening of an automobile. EXAMPLES
[0098] The surface of the glass plate was scratched using the method according to the present embodiment, and the strength, robustness, etc. were evaluated.
[0099] =Experiment a: Injuries during transportation= [Experiment a1. Strength test of flat glass plate] (Example a1-1) In the same manner as in the usual mass production process, the band-shaped glass sheet formed by the float method was cut into individual glass sheets, cut into a windshield shape, chamfered, and cleaned to obtain a flat untreated glass sheet (undamaged glass sheet) with a thickness of 2 mm before bending. In this series of processes, a roller conveyor was used as the conveying means. The multiple conveying rollers constituting the roller conveyor each had a radius of 50 mm (including the radius of the rubber ring) and were arranged at a pitch of 20 mm in the conveying direction. In addition, each conveying roller had a rubber ring with an axial length of 30 mm attached to the shaft at intervals of 50 mm, as shown in FIG. 6.
[0100] (Example a1-2) Among the series of steps in Example a1-1, in the step of cutting out individual glass sheets from the band-shaped glass sheet, that is, after the band-shaped glass sheet sent from the float bath is slowly cooled, until the glass sheet is actually cut out and sent to the subsequent processing step (cutting into a windshield shape), the conveying rollers scratched the conveying means-facing surface of the flat glass sheet before and after cutting out. The scratching function of the conveying rollers was imparted by wrapping a roughened film (3M Corporation's "Trizact (trademark) film 568XA", thickness 75 μm) around almost the entire surface of the rubber rings attached to the 20 conveying rollers so that the roughened surface was exposed. After scratching, the glass sheet was cut into a windshield shape, chamfered, and washed in the same manner as in Example a1-1, to obtain a scratched flat glass sheet with a thickness of 2 mm before bending.
[0101] The glass plates of Example a1-1 (Comparative Example) and Example a1-2 (Example) were evaluated as follows.
[0102] <Measurement of strength (breaking stress)> In each example, 50 small plate samples of 66 mm x 66 mm and 2 mm thick were cut out from one glass plate, and the strength of each small plate sample was measured as breaking stress (MPa). The breaking stress was measured by R30 in accordance with ISO1288-5 (2016). More specifically, a support ring with a diameter of 60 mm and a load ring with a diameter of 12 mm were used, and a load was applied by the load ring at a loading rate of 0.3 mm per minute to measure the breaking load. In both cases of Example a1-1 and Example a1-2, a load ring was placed on the non-facing surface side opposite to the conveying means facing surface, and the load was applied from the non-facing surface side. Furthermore, the breaking stress was calculated using the formula described in ISO1288-5 (2016).
[0103] <Evaluation of strength uniformity> The data on the strength of the 50 small plate samples was used to determine the frequency for every 50 MPa. FIG. 11 shows the frequency distribution for each of Examples a1-1 and a1-2.
[0104] Furthermore, based on the strength data of the small plate samples, the upper 20% (10 pieces) of strength data in the strength distribution of the untreated example a1-1 was extracted, and the average value (S 1-1U20 Similarly, for the damaged example a1-2, the strength data for the top 20% (10 pieces) of the strength distribution were extracted, and the average value (S 1-2U20 ) was calculated. The strength difference due to the damage, that is, the average value of the top 20% of the strength distribution of Example a1-1 (S 1-1U20 ) to the top 20% average value of the intensity distribution of Example a1-2 (S 1-2U20 ) minus the value (S 1-1U20 -S 1-2U20 ) was also calculated. Furthermore, the rate of decrease in strength due to damage was also calculated as {(S 1-1U20 -S 1-2U20 ) / (S 1-1U20 The results are shown in Table 1 and FIG.
[0105] <Evaluation of robustness> Similarly, based on the strength data of the 50 small plate samples, the strength data of the bottom 10% (5 pieces) of the strength distribution for the untreated example a1-1 was extracted, and the average value (S 1-1L10For the damaged example a1-2, the strength data for the bottom 10% (5 pieces) of the strength distribution was extracted, and the average value (S 1-2L10 ) was calculated. The strength difference due to the damage, that is, the average value of the bottom 10% of the strength distribution of Example a1-1 (S 1-1L10 ) to the bottom 10% average value of the intensity distribution of Example a1-2 (S 1-2L10 ) minus the value (S 1-1L10 -S 1-2L10 ) was also calculated. Furthermore, the rate of decrease in strength due to damage was also calculated as {(S 1-1L10 -S 1-2L10 ) / (S 1-1L10 The results are shown in Table 1 and FIG.
[0106] [Table 1]
[0107] From Table 1 and Figures 11 and 13, it was found that the in-plane strength variation was suppressed in the glass plate (Example a1-2) whose conveying means-facing surface was scratched, that is, the strength uniformity was improved. It was also found that the degree of decrease in the average strength as a whole and the degree of decrease in the strength of the low-strength region in the strength distribution were small, and the robustness of the glass plate was maintained.
[0108] [Experiment a2. Strength test of laminated glass] (Example a2-1) The 2 mm-thick flat untreated glass plates (unscratched glass plates) obtained in Example a1-1 were each bent in the same manner as in a normal mass production process, and two of the untreated glass plates were laminated with an interlayer (PVB resin) interposed therebetween and pressed to obtain a laminated glass (front glass) without scratching treatment. The obtained front glass was a curved laminated glass in which a 2 mm-thick glass plate, a 0.76 mm-thick PVB interlayer, and a 2 mm-thick glass plate were laminated.
[0109] (Example a2-2) In a series of steps for producing laminated glass (front glass) in Example a2-1, two scratched glass sheets produced in Example a1-2 were used instead of an untreated glass sheet (unscratched glass sheet) to obtain scratched laminated glass. When stacking the two scratched glass sheets produced in Example a1-2, they were arranged so that the scratched surfaces (surfaces facing the conveying means) of each glass sheet were both on the inside of the vehicle.
[0110] The laminated glasses of Example a2-1 (Comparative Example) and Example a2-2 (Example) were evaluated as follows.
[0111] <Measurement of strength (breaking stress)> In each example, 50 small plate samples of 100 mm x 100 mm were cut out from one laminated glass, and the strength of each small plate sample was measured as a breaking stress (MPa). The breaking stress was measured by R30 in accordance with ISO1288-5 (2016). More specifically, a support ring with a diameter of 60 mm and a load ring with a diameter of 12 mm were used, and a load was applied by the load ring at a loading rate of 1 mm per minute to measure the breaking load. In both cases of Example 2-1 and Example 2-2, the load was applied from the vehicle exterior surface of the vehicle exterior glass plate (the first surface 11, which is the vehicle exterior surface of the vehicle exterior glass plate 10 in FIG. 2). The breaking stress was calculated by determining the relationship between the load and the stress for two small plate samples using a strain gauge (Kyowa Electric Industry KFGS-5-120-D17-11).
[0112] <Evaluation of strength uniformity> Using the strength data of the 50 small plate samples, the frequency was calculated for every 50 MPa. Figure 12 shows the frequency distribution for each of Example a2-1 and Example a2-2.
[0113] Furthermore, based on the strength data of the small plate samples, the strength data of the top 20% (10 pieces) of the strength distribution for Example 2-1, which is untreated laminated glass, was extracted, and the average value (S 2-1U20 Similarly, for Example 2-2, which is a laminated glass obtained using scratched glass sheets, the strength data for the top 20% (10 pieces) of the strength distribution was extracted, and the average value (S 2-2U20) was calculated. The strength difference due to the damage, that is, the average value of the top 20% of the strength distribution in Example 2-1 (S 2-1U20 ) to the top 20% average value of the intensity distribution in Example 2-2 (S 2-2U20 ) minus the value (S 2-1U20 -S 2-2U20 ) was also calculated. Furthermore, the rate of decrease in strength due to damage was also calculated as {(S 2-1U20 -S 2-2U20 ) / (S 2-1U20 The results are shown in Table 2 and FIG.
[0114] <Evaluation of robustness> Similarly, based on the strength data of the 50 small plate samples, the strength data of the bottom 10% (5 pieces) of the strength distribution for the untreated laminated glass, Example a2-1, was extracted, and the average value (S 2-1L10 For Example 2-2, which is a laminated glass obtained using scratched glass sheets, the strength data for the bottom 10% (5 pieces) of the strength distribution was extracted, and the average value (S 2-2L10 ) was calculated. The strength difference due to the damage, that is, the average value of the bottom 10% of the strength distribution of Example a2-1 (S 2-1L10 ) to the bottom 10% average value of the intensity distribution of Example a2-2 (S 2-2L10 ) minus the value (S 2-1L10 -S 2-2L10 ) was also calculated. Furthermore, the rate of decrease in strength due to damage was also calculated as {(S 2-1L10 -S 2-2L10 ) / (S 2-1L10 The results are shown in Table 2 and FIG.
[0115] [Table 2]
[0116] 12 and 13, it was found that the laminated glass obtained using the glass sheet with the conveying means-facing surface scratched had reduced in-plane strength variation, i.e., had improved strength uniformity. It was also found that the degree of decrease in the average strength as a whole and the degree of decrease in the strength of the low-strength region in the strength distribution were small, and the robustness of the laminated glass as an automobile window glass was maintained.
[0117] =Experiment B: Damage caused by cleaning= [Experiment b1. Strength test of flat glass plate] (Example b1-1) Similar to the usual mass production process, the ribbon-shaped glass plate formed by the float method was cut into individual glass plates, cut into a windshield shape, chamfered, and cleaned to obtain a flat untreated glass plate (undamaged glass plate) with a thickness of 2 mm before bending.
[0118] (Example b1-2) After the flat undamaged glass plate obtained in Example b1-1 was thoroughly dried, a water-based liquid polishing agent containing cerium oxide ("Kiirobin" manufactured by Prostaff Co., Ltd.) was evenly applied to the upper surface of the undamaged glass plate (the surface opposite to the surface facing the conveying means) at a rate of 100g per square meter, and the glass plate was lightly polished evenly for 15 minutes per plate with an electric grinder ("Double Action Sander 28457" manufactured by 3M Co., Ltd.) equipped with a resin sheet ("Trizact Film 268XA-A5" manufactured by 3M Co., Ltd.), and then washed with water to perform a scratching treatment. As a result, a flat scratched glass plate with a thickness of 2 mm before bending was obtained.
[0119] The glass plates of Example b1-1 (Comparative Example) and Example b1-2 (Example) were evaluated as follows.
[0120] <Measurement of strength (breaking stress)> In each example, 50 small plate samples of 66 mm x 66 mm and 2 mm thick were cut out from one glass plate, and the strength of each small plate sample was measured as breaking stress (MPa). The breaking stress was measured by R30 in accordance with ISO1288-5 (2016). More specifically, a support ring with a diameter of 60 mm and a load ring with a diameter of 12 mm were used, and a load was applied by the load ring at a loading rate of 0.3 mm per minute to measure the breaking load. In both cases of Example b1-1 and Example b1-2, the load ring was placed on the side of the glass plate facing the conveying means during transportation, and the load was applied from the side facing the conveying means. Furthermore, the breaking stress was calculated using the formula described in ISO1288-5 (2016).
[0121] <Evaluation of strength uniformity> The data on the strength of the 50 small plate samples was used to determine the frequency for every 50 MPa. FIG. 14 shows the frequency distribution for each of Example b1-1 and Example b1-2.
[0122] Furthermore, based on the strength data of the small plate samples, the upper 20% (10 pieces) of strength data in the strength distribution of the untreated example b1-1 was extracted, and the average value (S 1-1U20 Similarly, for the damaged example b1-2, the strength data for the top 20% (10 pieces) of the strength distribution were extracted, and the average value (S 1-2U20 ) was calculated. The strength difference due to the damage, that is, the average value of the top 20% of the strength distribution of Example b1-1 (S 1-1U20 ) to the top 20% average value of the intensity distribution of example b1-2 (S 1-2U20 ) minus the value (S 1-1U20 -S 1-2U20 ) was also calculated. Furthermore, the rate of decrease in strength due to damage was also calculated as {(S 1-1U20 -S 1-2U20 ) / (S 1-1U20 )}×100(%). The results are shown in Table 3 and FIG.
[0123] <Evaluation of robustness> Similarly, based on the strength data of the 50 small plate samples, the strength data of the bottom 10% (5 pieces) of the strength distribution for the untreated example b1-1 was extracted, and the average value (S 1-1L10For the damaged example b1-2, the strength data for the bottom 10% (5 pieces) of the strength distribution were extracted, and the average value (S 1-2L10 ) was calculated. The strength difference due to the damage, that is, the average value of the bottom 10% of the strength distribution of Example b1-1 (S 1-1L10 ) to the bottom 10% average value of the intensity distribution of Example b1-2 (S 1-2L10 ) minus the value (S 1-1L10 -S 1-2L10 ) was also calculated. Furthermore, the rate of decrease in strength due to damage was also calculated as {(S 1-1L10 -S 1-2L10 ) / (S 1-1L10 )}×100(%). The results are shown in Table 3 and FIG.
[0124] [Table 3]
[0125] From Table 3 and Figures 14 and 16, it was found that the in-plane strength variation was suppressed in the glass plate (Example b1-2) whose conveying means-facing surface was scratched, that is, the strength uniformity was improved. It was also found that the degree of decrease in the average strength as a whole and the degree of decrease in the strength of the low-strength region in the strength distribution were small, and the robustness of the glass plate was maintained.
[0126] [Experiment b2. Strength test of laminated glass] (Example b2-1) The 2 mm-thick flat untreated glass plates (unscratched glass plates) obtained in Example b1-1 were each bent in the same manner as in a normal mass production process, and two of the untreated glass plates were laminated with an interlayer (PVB resin) interposed therebetween and pressed to obtain a laminated glass (front glass) without scratching treatment. The obtained front glass was a curved laminated glass in which a 2 mm-thick glass plate, a 0.76 mm-thick PVB interlayer, and a 2 mm-thick glass plate were laminated.
[0127] (Example b2-2) In a series of steps for producing laminated glass (front glass) in Example b2-1, two scratched glass plates produced in Example b1-2 were used instead of an untreated glass plate (unscratched glass plate) to obtain scratched laminated glass. When stacking the two scratched glass plates produced in Example b1-2, they were arranged so that the scratched surface of each glass plate (the surface opposite to the surface facing the conveying means) was on the inside of the vehicle.
[0128] The laminated glasses of Example b2-1 (Comparative Example) and Example b2-2 (Example) were evaluated as follows.
[0129] <Measurement of strength (breaking stress)> In each example, 50 small plate samples of 100 mm x 100 mm were cut out from one laminated glass, and the strength of each small plate sample was measured as a breaking stress (MPa). The breaking stress was measured by R30 in accordance with ISO1288-5 (2016). More specifically, a support ring with a diameter of 60 mm and a load ring with a diameter of 12 mm were used, and a load was applied by the load ring at a loading rate of 1 mm per minute to measure the breaking load. In both cases of Example b2-1 and Example b2-2, the load was applied from the vehicle exterior surface of the vehicle exterior glass plate (the first surface 11, which is the vehicle exterior surface of the vehicle exterior glass plate 10 in Figure 2). The breaking stress was calculated by determining the relationship between the load and stress for two small plate samples using a strain gauge (Kyowa Electric Industry KFGS-5-120-D17-11).
[0130] <Evaluation of strength uniformity> The data on the strength of the 50 small plate samples was used to determine the frequency for every 50 MPa. FIG. 15 shows the frequency distributions for each of Example b2-1 and Example b2-2.
[0131] Furthermore, based on the strength data of the small plate samples, the strength data of the top 20% (10 pieces) of the strength distribution for the untreated laminated glass, Example b2-1, was extracted, and the average value (S 2-1U20 Similarly, for Example b2-2, which is a laminated glass obtained using scratched glass sheets, the strength data for the top 20% (10 pieces) of the strength distribution was extracted, and the average value (S2-2U20 ) was calculated. The strength difference due to the damage, that is, the top 20% average value of the strength distribution of Example b2-1 (S 2-1U20 ) to the top 20% average value of the intensity distribution of example b2-2 (S 2-2U20 ) minus the value (S 2-1U20 -S 2-2U20 ) was also calculated. Furthermore, the rate of decrease in strength due to damage was also calculated as {(S 2-1U20 -S 2-2U20 ) / (S 2-1U20 The results are shown in Table 4 and FIG.
[0132] <Evaluation of robustness> Similarly, based on the strength data of the 50 small plate samples, the strength data of the bottom 10% (5 pieces) of the strength distribution for the untreated laminated glass, Example b2-1, was extracted, and the average value (S 2-1L10 For the laminated glass obtained using the scratched glass plate, Example b2-2, the strength data for the bottom 10% (5 pieces) of the strength distribution was also extracted, and the average value (S 2-2L10 ) was calculated. The strength difference due to the damage, that is, the average value of the bottom 10% of the strength distribution of Example b2-1 (S 2-1L10 ) to the bottom 10% average value of the intensity distribution of Example b2-2 (S 2-2L10 ) minus the value (S 2-1L10 -S 2-2L10 ) was also calculated. Furthermore, the rate of decrease in strength due to damage was also calculated as {(S 2-1L10 -S 2-2L10 ) / (S 2-1L10 The results are shown in Table 4 and FIG.
[0133] [Table 4]
[0134] From Table 4 and Figures 15 and 16, it was found that the laminated glass obtained using glass sheets in which the surface opposite to the surface facing the conveying means during conveying (the non-facing surface) was scratched had reduced in-plane strength variation, i.e., the strength uniformity was increased. It was also found that the degree of decrease in the average strength as a whole and the degree of decrease in the strength of the low-strength region in the strength distribution were small, and the robustness of the laminated glass as an automobile window glass was maintained.
[0135] =Experiment c: Scratching with sandpaper= (Example c1) Similar to the usual mass production process, the ribbon-shaped glass plate formed by the float method was cut into individual glass plates, cut into a windshield shape, chamfered, and cleaned to obtain a flat untreated glass plate (undamaged glass plate) with a thickness of 2 mm before bending.
[0136] (Example c2) After the flat undamaged glass plate obtained in Example c1 was thoroughly dried, it was placed on a flat table, and a #600 sandpaper was placed on the upper surface of the undamaged glass plate with the rough side facing down. A roller was then rolled once in one direction over the entire area of the sandpaper with a load of 2 kg from above the sandpaper. This was done so that the sandpaper did not move relative to the surface of the glass plate. As a result, a flat scratched glass plate with a thickness of 2 mm before bending was obtained.
[0137] (Example c3) Scratching was performed in the same manner as in Example c2, except that the grit size of the sandpaper used was changed to #2000.
[0138] (Example c4) Scratching was performed in the same manner as in Example c2, except that the grit size of the sandpaper used was changed to #8000.
[0139] (Example c5) The scratched glass plate obtained in Example c2 was stored under room temperature conditions (25° C., 60% RH) for about 90 days.
[0140] (Example c6) The scratched glass plate obtained in Example c2 was stored under humid conditions (50° C., 95% RH) for 1,000 hours (about 41 days).
[0141] (Example c7) The scratched glass plate obtained in Example c6 was heated in a heating furnace at a maximum temperature of 630° C. for 10 minutes.
[0142] The glass plates of Example c1 (Comparative Example) and Examples c2 to c7 (Examples) were evaluated as follows.
[0143] <Measurement of strength (breaking stress)> In each example, 50 small plate samples of 66 mm x 66 mm and 2 mm thick were cut out from one glass plate, and the strength of each small plate sample was measured as breaking stress (MPa). The breaking stress was measured by R30 in accordance with ISO1288-5 (2016). More specifically, a support ring with a diameter of 60 mm and a load ring with a diameter of 12 mm were used, and a load was applied by the load ring at a loading rate of 0.3 mm per minute to measure the breaking load. In both cases of Example b1-1 and Example b1-2, the load ring was placed on the side of the glass plate facing the conveying means during transportation, and the load was applied from the side facing the conveying means. Furthermore, the breaking stress was calculated using the formula described in ISO1288-5 (2016).
[0144] <Evaluation of strength uniformity and robustness> Using the strength data of the 50 small plate samples, the average, maximum, and minimum values of the fracture stress of each example were determined. The results of Examples c1 to c4 are shown in Figure 17, and the results of Examples c2 and c5 to c7 are shown in Figure 18.
[0145] From FIG. 17, the difference between the maximum value and the minimum value was smaller in the glass plates scratched with sandpaper (examples c2 to c4) compared to the unscratched glass plate (example c1). Therefore, it was found that the in-plane strength variation was suppressed by scratching, that is, the uniformity of the strength was improved. Furthermore, the minimum value was not so much lower in the glass plates scratched with sandpaper (examples c2 to c4) compared to the unscratched glass plate (example c1). Therefore, it was found that the robustness of the glass plate was maintained even after scratching. Furthermore, within the range of the grit size of the sandpaper used above, the smaller the grit size, the lower the maximum value can be, so it was found that the strength uniformity can be easily adjusted by changing the grit size of the sandpaper.
[0146] From FIG. 18, it was found that even when stored for a certain time or more or heated (examples c5 to c7), the fracture stress was sufficiently lower than the average fracture stress of the undamaged glass sheet (example c1), and the effect of the scratching was sufficiently maintained. Furthermore, from a comparison of the results of the glass sheet after room temperature storage (example c5) with the results of the glass sheet before storage (example c2), and from a comparison of the results of the glass sheet after wet storage (example c6) with the results of the glass sheet before storage (example c2), it was found that the effect of the scratching was sufficiently maintained when the scratched glass sheet was stored for a long period of time. Furthermore, from a comparison of the results of the glass sheet before heating (example c6) with the results of the glass sheet after heating (example c7), it was found that there was no significant change even when heated under conditions equivalent to the heating conditions of a bending furnace, and the effect of the scratching was maintained to a certain extent.
[0147] Specific embodiments are described below. [Appendix a1] A method for producing laminated glass for automobile windows, comprising: a step (A) of heating and bending two glass sheets; and a step (B) of laminating the two bent glass sheets together via an interlayer film, Before the step (A), at least one of the two flat glass plates is transported by a transport means, and a surface of the at least one glass plate facing the transport means is scratched by the transport means; In the step (B), the surface of the glass sheet facing the conveying means is disposed so as to face the interior side of the automobile when the laminated glass for automobile windows is installed in the automobile. [Appendix a2] The method for producing laminated glass for automobile windows according to Appendix a1, wherein the two flat glass plates are each scratched on their surfaces facing the conveying means. [Appendix a3] The injury, The difference between the average of the top 20% of the strength distribution of the surface facing the conveying means before the damage and the average of the top 20% of the strength distribution of the surface facing the conveying means after the damage is 50 MPa or more, and The difference between the average of the bottom 10% of the strength distribution of the surface facing the conveying means before the damage and the average of the bottom 10% of the strength distribution of the surface facing the conveying means after the damage is 50 MPa or less, The method for producing a laminated glass for automobile windows according to Appendix a1 or Appendix a2, wherein the strength is a breaking stress measured by a method described in ISO1288-5 (2016) by applying a load from the opposite side to the surface facing the conveying means. [Appendix a4] A method for producing a laminated glass for an automobile window according to any one of Appendices A1 to A3, wherein a rate of decrease due to the scratching in the average value of the top 20% of the strength distribution of the surface facing the transport means is 10% or more, and a rate of decrease due to the scratching in the average value of the bottom 10% of the strength distribution of the surface facing the transport means is 20% or less. [Appendix a5] The method for producing laminated glass for automobile windows according to any one of Appendix a1 to Appendix a4, wherein the conveying means is composed of a plurality of conveying rollers, and at least one of the conveying rollers has a rough surface. [Appendix a6] The method for producing a laminated glass for automobile windows according to any one of Appendix a1 to Appendix a5, wherein the conveying means is composed of a plurality of conveying rollers, and at least one of the angular velocity, the diameter, and the height of at least one of the conveying rollers is different from that of a conveying roller adjacent to the at least one of the conveying rollers. [Appendix a7] A laminated glass for automobile windows, comprising an exterior glass sheet and an interior glass sheet bonded together via an interlayer film, The vehicle exterior glass sheet has a first surface on the vehicle exterior side and a second surface on the vehicle interior side, The interior glass sheet has a third surface on an exterior side of the vehicle and a fourth surface on an interior side of the vehicle, Laminated glass for automotive windows that satisfies one or more of the following conditions 1 to 3. (Condition 1) The breaking stress measured according to a method conforming to ISO1288-5 (2016) is the strength. The difference between the average value of the top 20% of the strength distribution of the first surface and the average value of the top 20% of the strength distribution of the fourth surface is 50 MPa or more; and The difference between the average value of the bottom 10% of the strength distribution of the first surface and the average value of the bottom 10% of the strength distribution of the fourth surface is 50 MPa or less. (Condition 2) The breaking stress measured according to a method conforming to ISO1288-5 (2016) is taken as the strength. The difference between the average value of the top 20% of the strength distribution on the first surface and the average value of the top 20% of the strength distribution on the second surface is 50 MPa or more; and The difference between the average value of the bottom 10% of the strength distribution on the first surface and the average value of the bottom 10% of the strength distribution on the second surface is 50 MPa or less. (Condition 3) The breaking stress measured according to a method conforming to ISO1288-5(2016) is the strength. The difference between the average value of the top 20% of the strength distribution of the third surface and the average value of the top 20% of the strength distribution of the fourth surface is 50 MPa or more; and The difference between the average value of the bottom 10% of the strength distribution on the third surface and the average value of the bottom 10% of the strength distribution on the fourth surface is 50 MPa or less. [Appendix a8] A laminated glass for automobile windows, comprising an exterior glass sheet and an interior glass sheet bonded together via an interlayer film, The laminated glass for automotive windows as described in Appendix A7, wherein the average value of the top 20% of the fracture stress distribution in the transmission region, measured by a method in accordance with ISO1288-5(2016) while applying a load from the outside of the vehicle, is 500 MPa or less. [Appendix a9] The laminated glass for automobile windows according to Appendix A7 or A8, which is a windshield. [Appendix a10] An automobile equipped with a laminated glass for automobile windows according to any one of appendices a7 to a9. [Appendix b1] A method for producing laminated glass for automobile windows, comprising: a step (A) of heating and bending two glass sheets; and a step (B) of laminating the two bent glass sheets together via an interlayer film, Prior to the step (A), at least one of the two flat glass plates is transported by a transport means, and a non-facing surface of the at least one glass plate opposite to the surface facing the transport means is scratched; In the step (B), the non-opposing surfaces of the glass plates are arranged so as to face the interior side of the automobile when the automobile window laminated glass is installed in the automobile. [Appendix b2] The method for manufacturing laminated glass for automobile windows according to Appendix B1, wherein the non-facing surfaces of the two flat glass plates are each scratched. [Appendix b3] The injury, The difference between the average of the top 20% of the strength distribution of the conveying means facing surface and the average of the top 20% of the strength distribution of the non-facing surface is 50 MPa or more, and The difference between the average of the bottom 10% of the strength distribution of the conveying means facing surface and the average of the bottom 10% of the strength distribution of the non-facing surface is 50 MPa or less, The method for producing a laminated glass for automobile windows according to Appendix b1 or Appendix b2, wherein the strength is a breaking stress measured by a method described in ISO1288-5(2016) by applying a load from the non-opposing surface. [Appendix b4] A method for producing laminated glass for automobile windows according to any one of Appendix B1 to B3, wherein a rate of decrease due to the scratching of the average value of the top 20% of the strength distribution of the non-opposing surfaces is 10% or more, and a rate of decrease due to the scratching of the average value of the bottom 10% of the strength distribution of the non-opposing surfaces is 20% or less. [Appendix b5] A method for manufacturing laminated glass for automobile windows described in any one of Appendix B1 to Appendix B4, in which the scratching is performed by contacting a scratching tool with the non-opposing surface and moving it relative to the non-opposing surface. [Appendix b6] A method for producing laminated glass for automobile windows as described in appendix B55, wherein the scratching is carried out in the presence of an abrasive. [Appendix b7] A method for manufacturing laminated glass for automobile windows as described in Appendix B5 or B6, in which water or an aqueous solution is interposed between the scratching tool and the non-facing surface. [Appendix b8] A laminated glass for automobile windows, comprising an exterior glass sheet and an interior glass sheet bonded together via an interlayer film, The vehicle exterior glass sheet has a first surface on the vehicle exterior side and a second surface on the vehicle interior side, The interior glass sheet has a third surface on an exterior side of the vehicle and a fourth surface on an interior side of the vehicle, Laminated glass for automotive windows that satisfies one or more of the following conditions 1 to 3. (Condition 1) The breaking stress measured according to a method conforming to ISO1288-5 (2016) is the strength. The difference between the average value of the top 20% of the strength distribution of the first surface and the average value of the top 20% of the strength distribution of the fourth surface is 50 MPa or more; and The difference between the average value of the bottom 10% of the strength distribution of the first surface and the average value of the bottom 10% of the strength distribution of the fourth surface is 50 MPa or less. (Condition 2) The breaking stress measured according to a method conforming to ISO1288-5 (2016) is taken as the strength. The difference between the average value of the top 20% of the strength distribution on the first surface and the average value of the top 20% of the strength distribution on the second surface is 50 MPa or more; and The difference between the average value of the bottom 10% of the strength distribution on the first surface and the average value of the bottom 10% of the strength distribution on the second surface is 50 MPa or less. (Condition 3) The breaking stress measured according to a method conforming to ISO1288-5(2016) is the strength. The difference between the average value of the top 20% of the strength distribution of the third surface and the average value of the top 20% of the strength distribution of the fourth surface is 50 MPa or more; and The difference between the average value of the bottom 10% of the strength distribution on the third surface and the average value of the bottom 10% of the strength distribution on the fourth surface is 50 MPa or less. [Appendix b9] A laminated glass for automobile windows, comprising an exterior glass sheet and an interior glass sheet bonded together via an interlayer film, The laminated glass for automobile windows according to appendix b8, wherein the average value of the top 20% of the fracture stress distribution in the transmission region, measured by a method conforming to ISO1288-5(2016) while applying a load from the outside of the vehicle, is 500 MPa or less. [Appendix b10] The laminated glass for automobile windows according to Appendix B8 or B9, which is a windshield. [Appendix b11] An automobile equipped with a laminated glass for automobile windows according to any one of Appendix B8 to Appendix B10.
[0148] This application claims priority based on Japanese Patent Application No. 2021-071142 and Japanese Patent Application No. 2021-071143, filed on April 20, 2021, the entire contents of which are incorporated herein by reference. [Explanation of symbols]
[0149] 1. Laminated glass 10. Vehicle exterior glass panel 11 Page 1 12 Side 2 20. Car interior glass panel 21 Page 3 22 Page 4 30 Interlayer 50 Means of transportation 51, 51a, 51b Conveyor rollers 100 Automobiles F2 Non-opposing surface Da Axial direction of the conveyor roller Dt Transport direction G Flat glass plate
Claims
1. A method for producing laminated glass for automobile windows, comprising: a step (A) of heating and bending two glass sheets; and a step (B) of laminating the two bent glass sheets together via an interlayer film, Prior to the step (A), at least one of the two flat glass plates is transported by a transport means, and a surface of the at least one glass plate facing the transport means or a non-facing surface opposite to the surface facing the transport means is scratched; In the step (B), the damaged surface is disposed so as to face the interior side of the automobile when the laminated glass for automobile windows is installed in the automobile.
2. The injury, The difference between the average of the top 20% of the strength distribution of the scratched surface and the average of the top 20% of the strength distribution of the surface before scratching is 50 MPa or more; and The difference between the average of the bottom 10% of the strength distribution of the scratched surface and the average of the bottom 10% of the strength distribution of the surface before the scratching is 50 MPa or less; The method for producing a laminated glass for automobile windows according to claim 1, wherein the strength is a breaking stress measured by a method described in ISO1288-5 (2016) by applying a load from the opposite side to the surface to which the strength is measured.
3. 3. The method for producing a laminated glass for an automobile window according to claim 1, wherein a rate of decrease due to the scratching of an average value of top 20% of the strength distribution of the surface is 10% or more, and a rate of decrease due to the scratching of an average value of bottom 10% of the strength distribution of the surface is 20% or less.
4. 3. The method for producing a laminated glass for an automobile window according to claim 1, further comprising the step of scratching each of the two flat glass sheets on a surface facing the conveying means.
5. The damage is performed by the conveying means; 5. The method for producing laminated glass for automobile windows according to claim 4, wherein the transport means is composed of a plurality of transport rollers, at least one of the transport rollers having a rough surface.
6. The damage is performed by the conveying means; 5. The method for producing a laminated glass for an automobile window according to claim 4, wherein the transport means is composed of a plurality of transport rollers, and at least one of the angular velocity, the diameter, and the height of at least one of the transport rollers is different from that of a transport roller adjacent to the at least one transport roller.
7. The method for producing a laminated glass for an automobile window according to claim 1 , further comprising the step of scratching the non-opposing surfaces of the two flat glass plates.
8. The method for producing a laminated glass for an automobile window according to claim 7, wherein the scratching is performed by bringing a scratching tool into contact with the non-opposing surface and moving the scratching tool relatively to the non-opposing surface.
9. The method for producing a laminated glass for an automobile window according to claim 8, wherein the scratching is carried out in the presence of an abrasive.
10. The method for producing a laminated glass for an automobile window according to claim 9, wherein water or an aqueous solution is interposed between the scratching tool and the non-facing surface.
11. A laminated glass for automobile windows, comprising an exterior glass sheet and an interior glass sheet bonded together via an interlayer film, The vehicle exterior glass sheet has a first surface on the vehicle exterior side and a second surface on the vehicle interior side, the interior side glass sheet has a third surface on an exterior side of the vehicle and a fourth surface on an interior side of the vehicle, A laminated glass for automobile windows, which satisfies one or more of the following (Condition 1) to (Condition 3): (Condition 1) The breaking stress measured by a method conforming to ISO 1288-5 (2016) is the strength, The difference between the average value of the top 20% of the strength distribution on the first surface and the average value of the top 20% of the strength distribution on the fourth surface is 50 MPa or more; and The difference between the average value of the bottom 10% of the strength distribution on the first surface and the average value of the bottom 10% of the strength distribution on the fourth surface is 50 MPa or less. (Condition 2) The breaking stress measured by a method conforming to ISO 1288-5 (2016) is the strength, The difference between the average value of the top 20% of the strength distribution on the first surface and the average value of the top 20% of the strength distribution on the second surface is 50 MPa or more; and The difference between the average value of the bottom 10% of the strength distribution on the first surface and the average value of the bottom 10% of the strength distribution on the second surface is 50 MPa or less. (Condition 3) The breaking stress measured by a method conforming to ISO 1288-5 (2016) is the strength, The difference between the average value of the top 20% of the strength distribution on the third surface and the average value of the top 20% of the strength distribution on the fourth surface is 50 MPa or more; and The difference between the average value of the bottom 10% of the strength distribution on the third surface and the average value of the bottom 10% of the strength distribution on the fourth surface is 50 MPa or less.
12. A laminated glass for automobile windows, comprising an exterior glass sheet and an interior glass sheet bonded together via an interlayer film, The laminated glass for automobile windows according to claim 11, wherein the average value of the top 20% of the fracture stress distribution in the transmission region, measured by a method in accordance with ISO1288-5 (2016) while applying a load from the outside of the vehicle, is 500 MPa or less.
13. The laminated glass for an automobile window according to claim 11 or 12, which is a windshield.
14. An automobile equipped with the laminated glass for automobile windows according to claim 11 or 12.
Citation Information
Patent Citations
JP1972000827B1
JP1972016827B1
Water-repellent and oil-repellent article and its production
JP1997309745A
Improving edge strength of flat glass
JP1998506367A
Method of manufacturing glass substrate and glass substrate obtained by the method
JP2004059419A